Quantum dot-polymer composite and display device including the composite
By adopting core-shell quantum dot structure and specific molar ratio and shell structure, environmentally friendly cadmium-free quantum dot-polymer composites are developed, solving the problem of insufficient luminescence properties and stability in the prior art, and achieving efficient luminescence performance.
Patent Information
- Application Number
- CN202011238165.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-11-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-11-09
AI Technical Summary
The prior art is difficult to develop an environmentally friendly cadmium-free quantum dot with improved luminescence properties, especially in maintaining stability and improving luminescence efficiency.
A core-shell quantum dot structure is adopted, in which the semiconductor nanocrystal core includes indium, zinc and phosphorus, and the semiconductor nanocrystal shell includes zinc, selenium and sulfur, and a cadmium-free quantum dot-polymer composite is constructed through specific molar ratios and shell structures.
Environmentally friendly cadmium-free quantum dots are achieved, with improved luminescence properties and stability, with quantum efficiency of 75% or higher, and with a blue light conversion efficiency of 30% or higher after heat treatment at 180°C.
Smart Images

Figure CN112778999B_ABST
Abstract
Description
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2019-0142622 filed in the Korean Intellectual Property Office on November 8, 2019, the entire contents of which are incorporated herein by reference. Technical Field
[0002] Disclosed are a quantum dot, a composite comprising the quantum dot, a method for preparing the quantum dot, and a display device comprising the composite. Background Art
[0003] Quantum dots (i.e., nanometer-sized semiconductor nanocrystals) can have different band gaps by controlling the size and composition of the nanocrystals, and can therefore emit light of various photoluminescence wavelengths. Quantum dots can exhibit electroluminescent properties and photoluminescent properties. In the wet chemical process of making quantum dots, organic materials such as ligands are coordinated to the surface of semiconductor nanocrystals during crystal growth to provide quantum dots with controlled particle size and luminescent properties. The luminescent properties of quantum dots can be applied to various fields including as light-emitting elements in electronic displays, for example. It is desirable to develop a quantum dot with environmentally friendly and improved luminescent properties. Summary of the invention
[0004] Embodiments provide an environmentally friendly (eg, cadmium-free) quantum dot that can exhibit improved luminescent properties and improved stability.
[0005] Another embodiment provides a method for preparing the quantum dots.
[0006] Another embodiment provides a quantum dot-polymer composite including the quantum dots.
[0007] Another embodiment provides a stack structure and an electronic (eg, display) device including the quantum dot-polymer composite.
[0008] In an embodiment, the quantum dot-polymer composite comprises a polymer matrix and quantum dots dispersed in the polymer matrix.
[0009] The quantum dots include core-shell quantum dots comprising a semiconductor nanocrystal core and a semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, wherein the semiconductor nanocrystal core includes indium, zinc and phosphorus, and the semiconductor nanocrystal shell includes zinc, selenium and sulfur.
[0010] wherein the core-shell quantum dots do not include cadmium, and the core-shell quantum dots are configured to emit green light,
[0011] The core-shell quantum dots have a molar ratio of phosphorus to indium of greater than or equal to about 0.75:1, and the core-shell quantum dots have a molar ratio of zinc to indium of greater than or equal to about 35:1.
[0012] The core-shell quantum dots may have a molar ratio of sulfur to selenium (S:Se) of less than or equal to about 1:1.
[0013] The core-shell quantum dots may have a molar ratio of sulfur to selenium of less than or equal to about 0.9:1.
[0014] The core-shell quantum dots may have a molar ratio of sulfur to selenium of greater than or equal to about 0.3:1.
[0015] The maximum (photo)luminescence peak wavelength of green light may be greater than or equal to about 500 nanometers (nm).
[0016] The core-shell quantum dots may have a molar ratio of phosphorus to indium greater than or equal to about 0.8:1 and less than or equal to about 0.98:1 and / or a molar ratio of zinc to indium greater than or equal to about 40:1 and less than or equal to about 55:1.
[0017] The maximum (photo)luminescence peak wavelength of the green light may be less than or equal to about 550 nm.
[0018] The maximum (photo)luminescence peak wavelength of green light may be less than or equal to about 538 nm.
[0019] The quantum efficiency of the quantum dot-polymer composite may be greater than or equal to about 75%.
[0020] The quantum efficiency of the quantum dot-polymer composite may be greater than or equal to about 80%.
[0021] The quantum efficiency of the quantum dot-polymer composite may be greater than or equal to about 85%.
[0022] The quantum dot-polymer composite may have a blue light conversion efficiency greater than or equal to about 30% after heat treatment at 180° C. for 30 minutes.
[0023] The core-shell quantum dots may be configured to have a valley depth (VD) greater than or equal to about 0.4, as defined by the following formula:
[0024] 1-(Abs valley / Abs first )=VD
[0025] Among them, Abs first is the absorbance at the first absorption peak, Abs valley It is the absorbance at the lowest point of the valley adjacent to the first absorption peak.
[0026] The valley depth may be greater than or equal to approximately 0.5.
[0027] The core-shell quantum dots may have a molar ratio of phosphorus to indium of less than or equal to about 1.2:1.
[0028] The core-shell quantum dots may have a molar ratio of zinc to indium of less than or equal to about 55:1.
[0029] The core-shell quantum dots may have a molar ratio of the sum of sulfur and selenium to indium of greater than or equal to about 10:1, eg, greater than or equal to about 30:1 or greater than or equal to about 35:1.
[0030] The core-shell quantum dots may have a molar ratio of the sum of sulfur and selenium to indium of less than or equal to about 45:1, such as less than or equal to about 42:1.
[0031] The semiconductor nanocrystal shell may include a first shell layer including zinc and selenium and a second shell layer including zinc and sulfur and disposed on the first shell layer.
[0032] The first shell layer may be disposed directly on the semiconductor nanocrystal core.The first shell layer may or may not include sulfur.
[0033] The second shell layer may not include selenium.
[0034] The thickness of the second shell layer may be less than about 0.7 nm.
[0035] The second shell layer can be the outermost layer of the semiconductor nanocrystal shell.
[0036] In a low-temperature photoluminescence spectrum analysis of core-shell quantum dots measured at a temperature of 77K (e.g., using a light source with a wavelength of 400nm), the ratio of the area of the well emission peak (e.g., present at a wavelength greater than or equal to about 600nm or 650nm) (e.g., the peak integrated area determined by deconvolution of the maximum photoluminescence peak in a region spaced approximately -0.45eV or more from its central wavelength) to the total area of the maximum emission peak (hereinafter, also referred to as the deep well ratio) may be less than or equal to about 4%, less than or equal to about 3%, or less than or equal to about 2%.
[0037] Core-shell quantum dots may not include gallium.
[0038] The core-shell quantum dots may have a size (or average particle size) less than or equal to about 7 nm.
[0039] The polymer matrix may include linear polymers, cross-linked polymers, or combinations thereof.
[0040] The cross-linked polymer may include a thiol-ene polymer, a cross-linked poly(meth)acrylate, a cross-linked polyurethane, a cross-linked epoxy resin, a cross-linked vinyl polymer, a cross-linked silicone resin, or a combination thereof.
[0041] The linear polymer may include repeating units derived from monomers including carbon-carbon unsaturated bonds and optionally carboxylate groups.
[0042] The cross-linked polymer may include a polymerization product of a (photo)polymerizable monomer including a carbon-carbon double bond, a polymerization product between a (photo)polymerizable monomer and a polythiol compound having at least two thiol groups at the terminal, or a combination thereof.
[0043] The polymer matrix may include a carboxyl-containing compound,
[0044] Among them, the carboxyl-containing compounds may include:
[0045] A monomer combination or a copolymer of a monomer combination, wherein the monomer combination includes a first monomer, a second monomer, and an optional third monomer, wherein the first monomer includes a carboxyl group and a carbon-carbon double bond, the second monomer includes a carbon-carbon double bond and a hydrophobic portion and does not include a carboxyl group, and the optional third monomer includes a carbon-carbon double bond and a hydrophilic portion and does not include a carboxyl group;
[0046] A polymer containing multiple aromatic rings having a backbone structure in which two aromatic rings are bonded to a quaternary carbon atom and including a carboxyl group (-COOH), the quaternary carbon atom being a constituent atom of another ring portion in the main chain; or
[0047] A combination of them.
[0048] The carboxyl-containing compound can have an acid value greater than or equal to about 50 mg KOH / g. The carboxyl-containing compound can have a molecular weight greater than or equal to about 100 g / mol (e.g., greater than or equal to about 400 g / mol) and less than or equal to about 50,000 g / mol (e.g., less than or equal to about 15,000 g / mol, less than or equal to about 13,000 g / mol, less than or equal to about 10,000 g / mol, or less than or equal to about 8,500 g / mol).
[0049] The quantum dot-polymer composites may also include metal oxide particles dispersed in the polymer matrix.
[0050] The quantum dot-polymer composite can have the shape of a patterned film.
[0051] In another embodiment, the composition may include the core-shell quantum dots (eg, a plurality of the core-shell quantum dots), a dispersant, and an (organic) solvent. The dispersant may include a carboxyl-containing binder (or a carboxyl-containing binder polymer).
[0052] The composition may also comprise a (photo)polymerizable monomer comprising a carbon-carbon double bond and optionally a (thermal or photo)initiator.
[0053] Carboxyl-containing binder polymers may include:
[0054] A copolymer of a monomer combination, the monomer combination comprising a first monomer, a second monomer, and an optional third monomer, the first monomer comprising a carboxyl group and a carbon-carbon double bond, the second monomer comprising a carbon-carbon double bond and a hydrophobic portion and excluding a carboxyl group, and the optional third monomer comprising a carbon-carbon double bond and a hydrophilic portion and excluding a carboxyl group;
[0055] A polymer containing multiple aromatic rings having a backbone structure in which two aromatic rings are bonded to a quaternary carbon atom and including a carboxyl group (-COOH), the quaternary carbon atom being a constituent atom of another ring portion in the main chain; or
[0056] A combination of them.
[0057] In another embodiment, a display device includes a light source and a photoluminescent element, wherein the photoluminescent element includes the quantum dot-polymer composite described above, and the light source is configured to provide incident light to the photoluminescent element.
[0058] The incident light may have a peak wavelength of about 440 nm to about 470 nm (or about 460 nm). The incident light may also include, for example, green light having a wavelength of about 500 nm to about 560 nm.
[0059] The photoluminescent element may include a sheet of quantum dot-polymer composite.
[0060] The photoluminescent element is a stacked structure including a substrate and a light-emitting layer disposed on the substrate, and
[0061] The light emitting layer may include a pattern of quantum dot-polymer composites.
[0062] The pattern may include one or more repeating portions that emit light of a predetermined wavelength.
[0063] The pattern may include a first repeating portion that emits a first light.
[0064] The pattern may further include a second repeating portion that emits a second light having a different central wavelength than the first light.
[0065] The display device may be configured to exhibit a color reproducibility greater than or equal to about 80% under BT2020.
[0066] In another embodiment, a population of quantum dots may include core-shell quantum dots comprising a semiconductor nanocrystal core and a semiconductor nanocrystal shell, the semiconductor nanocrystal core comprising indium, zinc, and phosphorus, the semiconductor nanocrystal shell being disposed on the semiconductor nanocrystal core, the semiconductor nanocrystal shell comprising zinc, selenium, and sulfur,
[0067] Among them, the core-shell quantum dots do not include cadmium,
[0068] The core-shell quantum dots have a molar ratio of phosphorus to indium greater than or equal to about 0.75:1 and less than or equal to about 1.5:1,
[0069] The core-shell quantum dots have a molar ratio of zinc to indium of greater than or equal to about 33:1,
[0070] The core-shell quantum dots are configured to emit green light having a maximum (photo)luminescence peak wavelength less than or equal to about 550 nm.
[0071] The core-shell quantum dots may have a phosphorus to indium molar ratio of greater than or equal to about 0.8: 1. The core-shell quantum dots may have a phosphorus to indium molar ratio of less than or equal to about 1.4: 1, less than or equal to about 1.3: 1, less than or equal to about 1.2: 1, or less than or equal to about 1.1: 1.
[0072] The core-shell quantum dots may have a molar ratio of zinc to indium of greater than or equal to about 38:1, greater than or equal to about 40:1, greater than or equal to about 43:1, greater than or equal to about 44:1, greater than or equal to about 45:1, or greater than or equal to about 46:1.
[0073] The core-shell quantum dots may have a molar ratio of sulfur to selenium of less than or equal to about 1:1.
[0074] The core-shell quantum dots may have a molar ratio of sulfur to selenium of less than or equal to about 0.7:1, less than or equal to about 0.65:1, less than or equal to about 0.61:1, or less than or equal to about 0.6:1.
[0075] The core-shell quantum dots may have a molar ratio of sulfur to selenium of greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, or greater than or equal to about 0.45:1.
[0076] The population of quantum dots may have an average particle size less than or equal to about 7 nm. The population of quantum dots may have an average particle size greater than or equal to about 5 nm.
[0077] The population of quantum dots can have a size distribution (particle size standard deviation) (of the average particle size) of less than or equal to about 17%.
[0078] The population of quantum dots can have a size distribution of less than or equal to about 15% of the average particle size.
[0079] The green light may have a maximum (photo)luminescence peak wavelength less than or equal to about 530 nm. The green light may have a maximum (photo)luminescence peak wavelength less than or equal to about 525 nm. The green light may have a maximum (photo)luminescence peak wavelength less than or equal to about 520 nm.
[0080] The core-shell quantum dots may have a quantum yield (or quantum efficiency) of greater than or equal to about 80%.
[0081] The core-shell quantum dots can have a quantum yield greater than or equal to about 85%.
[0082] In a photoluminescence spectrum of the quantum dot population measured at 77K, the deep well ratio may be less than or equal to about 4%, less than or equal to about 3%, or less than or equal to about 2%.
[0083] In an embodiment, the semiconductor nanocrystal core includes a layer structure of InP / InZnP / InP, wherein a concentration gradient of zinc may increase from the center of the semiconductor nanocrystal core toward the surface and then decrease.
[0084] In another embodiment, the method for manufacturing the above quantum dot population comprises the following steps:
[0085] preparing a semiconductor nanocrystal core comprising indium, zinc and phosphorus; and
[0086] reacting a zinc shell precursor with at least one of a selenium precursor and a sulfur precursor in the presence of the semiconductor nanocrystal core and the first organic ligand to form a semiconductor nanocrystal shell including zinc, selenium and sulfur on the semiconductor nanocrystal core,
[0087] The step of preparing the semiconductor nanocrystal core comprises: preparing an indium precursor solution by heating an indium compound in the presence of a second organic ligand and an organic solvent; optionally heating the indium precursor solution; and mixing the indium precursor solution (such as optionally heated) with a phosphorus precursor and a zinc core precursor simultaneously or sequentially, and performing a reaction at a reaction temperature.
[0088] Therein, the ratio between the precursors (and optionally the mixing method therebetween) is adjusted to obtain quantum dots having the aforementioned composition.
[0089] The step of mixing the phosphorus precursor may be performed two or more times. The step of mixing the zinc precursor may be performed two or more times. The method may also include adding an indium precursor solution to the reaction mixture (e.g., at least once, twice, or more times).
[0090] In the above method, the zinc shell precursor may not include halogen.
[0091] The step of forming the shell may include implanting a halide and a Lewis base of an additional metal, and the additional metal may include aluminum, magnesium, gallium, antimony, titanium, or a combination thereof.
[0092] Lewis bases may include R 3 PO (wherein R is a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof).
[0093] The step of forming the shell may also include implanting zinc halide.
[0094] The zinc halide may include zinc chloride.
[0095] In an embodiment, the quantum dot-polymer composite comprises a polymer matrix and the quantum dots are dispersed in the polymer matrix.
[0096] wherein the quantum dots include core-shell quantum dots comprising a semiconductor nanocrystal core and a semiconductor nanocrystal shell, the semiconductor nanocrystal core comprising indium, zinc and phosphorus, the semiconductor nanocrystal shell being disposed on the semiconductor nanocrystal core and comprising zinc, selenium and sulfur,
[0097] The semiconductor nanocrystal core includes a layer structure of InP / InZnP / InP, wherein the concentration gradient of zinc increases from the center of the semiconductor nanocrystal core toward the surface and then decreases,
[0098] wherein the core-shell quantum dots have a molar ratio of phosphorus to indium greater than or equal to about 0.75:1 and less than or equal to 1.2:1, and a molar ratio of zinc to indium greater than or equal to about 35:1 and less than or equal to 55:1,
[0099] Wherein the core-shell quantum dots do not include cadmium, and the core-shell quantum dots are configured to emit green light.
[0100] A display device is also described, the display device comprising a light source and a light emitting element, wherein the light emitting element comprises a color filter,
[0101] The light source is configured to provide incident light to the light emitting element.
[0102] In an embodiment, the color filter includes a patterned film of the aforementioned quantum dot-polymer composite, and the display device may further include a liquid crystal layer.
[0103] The core-shell quantum dots and quantum dot-polymer composites including core-shell quantum dots according to the embodiments can exhibit improved luminescent properties. The core-shell quantum dots of the embodiments can be used in various display devices and biomarkers (e.g., biosensors, bioimaging, etc.), photodetectors, solar cells, hybrid composites, etc. The improved luminescent efficiency of the core-shell quantum dots according to the embodiments can present potential usefulness in photoluminescent color filters based on quantum dots. Such photoluminescent color filters can, for example, be used in various blue light sources, such as blue light OLEDs, blue light emitting micro-LEDs, and liquid crystal displays including blue light sources. BRIEF DESCRIPTION OF THE DRAWINGS
[0104] Figure 1 This is a diagram for explaining the concept of valley depth.
[0105] Figure 2 is a schematic diagram showing a cross section of a display device according to an embodiment.
[0106] Figure 3A is a schematic diagram showing a cross section of a display device according to an embodiment.
[0107] Figure 3B is a schematic diagram showing a cross section of a display device according to an embodiment.
[0108] Figure 4 is a schematic diagram showing a cross section of a display device according to an embodiment.
[0109] Figure 5 is a schematic diagram illustrating a pattern forming process using a composition according to an embodiment.
[0110] Figure 6 is a graph showing the results of low-temperature photoluminescence analysis of quantum dots prepared in Example. DETAILED DESCRIPTION
[0111] The advantages and features of the present disclosure and methods for achieving the same will become apparent with reference to the following example embodiments and the accompanying drawings. However, the embodiments should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0112] Unless otherwise defined, all terms (including technical terms and scientific terms) in the specification may be defined as commonly understood by those skilled in the art. It will also be understood that terms (such as those defined in general dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant field, and will not be interpreted ideally or exaggeratedly unless explicitly defined. The terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting.
[0113] As used herein, the singular forms "a", "an", and "the" are intended to include plural forms including "at least one", unless the context clearly indicates otherwise. "At least one" is not to be interpreted as limiting "one" or "one". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. It will also be understood that when the terms "include" and / or "comprising" or their variations are used in this specification, the stated features, regions, integers, steps, operations, elements and / or components are indicated, but the presence or addition of one or more other features, regions, integers, steps, operations, elements, components and / or groups thereof is not excluded.
[0114] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity. Like reference numerals refer to like elements throughout the specification.
[0115] It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, the element can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.
[0116] As used herein, when no definition is otherwise provided, "substituted" refers to a compound in which a hydrogen is replaced by a substituent selected from the group consisting of C1 to C30 alkyl, C2 to C30 alkenyl, C2 to C30 alkynyl, C6 to C30 aryl, C7 to C30 alkylaryl, C1 to C30 alkoxy, C1 to C30 heteroalkyl, C3 to C30 heteroalkylaryl, C3 to C30 cycloalkyl, C3 to C30 (or C3 to C15) cycloalkenyl, C3 to C30 (or C6 to C30) cycloalkynyl, C2 to C30 heterocycloalkyl, halogen (-F, -Cl, -Br or -I), hydroxyl (-OH), nitro (-NO 2 ), cyano (-CN), amino or amine (-NRR', wherein R and R' are independently hydrogen or C1 to C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2 ), thiol group (-SH), ester group (-C(=O)OR, wherein R is C1 to C6 alkyl or C6 to C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic cation or an inorganic cation), sulfonic acid group (-SO3 H) or its salt (-SO 3 M, wherein M is an organic cation or an inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , wherein M is an organic cation or an inorganic cation) and combinations thereof.
[0117] Here, the “monovalent organic functional group” refers to a C1 to C30 alkyl group, a C2 to C30 alkenyl group, a C2 to C30 alkynyl group, a C6 to C30 aryl group, a C7 to C30 alkylaryl group, a C1 to C30 alkoxy group, a C1 to C30 heteroalkyl group, a C3 to C30 heteroalkylaryl group, a C3 to C30 cycloalkyl group, a C3 to C30 (or C3 to C15) cycloalkenyl group, a C3 to C30 (or C6 to C30) cycloalkynyl group or a C2 to C30 heterocycloalkyl group.
[0118] As used herein, when no definition is otherwise provided, the term “hetero” means including at least one (eg, one to three) heteroatoms selected from N, O, S, Si and P.
[0119] As used herein, "alkylene" refers to a straight or branched saturated aliphatic hydrocarbon group having a valence of at least two and optionally substituted with at least one substituent. As used herein, "arylene" refers to a functional group having a valence of at least two and optionally substituted with at least one substituent obtained by removing at least two hydrogens from at least one aromatic ring.
[0120] In addition, the "aliphatic organic group" refers to a C1 to C30 straight chain or branched alkyl group, the "aromatic organic group" refers to a C6 to C30 aryl group or a C2 to C30 heteroaryl group, and the "alicyclic organic group" refers to a C3 to C30 cycloalkyl group, a C3 to C30 cycloalkenyl group and a C3 to C30 cycloalkynyl group.
[0121] As used herein, "(meth)acrylate" refers to acrylate and / or methacrylate.
[0122] Here, the blue light conversion rate (blue light conversion efficiency: CE) refers to the ratio of the amount of light emitted by the quantum dot-polymer complex to the amount of light absorbed by the quantum dot-polymer complex from the excitation light (e.g., blue light). The total amount of light (B) of the excitation light is obtained by integrating the PL spectrum, the PL spectrum of the quantum dot (polymer) complex film is measured, the amount of light (A) of the green or red wavelength light emitted from the quantum dot (polymer) complex film and the amount of light (B') of the excitation light are obtained, and the blue light conversion rate and the blue light absorption rate are obtained by the following equations:
[0123] [A / (B-B')]×100%=Blue light conversion rate (%)
[0124] [(B-B') / B] x 100% = blue light absorptivity of a single film (%).
[0125] In embodiments, "dispersion" may refer to a dispersion in which the dispersed phase is a solid and the continuous phase includes a liquid or a solid. In embodiments, "dispersion" may refer to a colloidal dispersion in which the dispersed phase has a size greater than or equal to about 1 nm, e.g., greater than or equal to about 2 nm, greater than or equal to about 3 nm, or greater than or equal to about 4 nm and a few micrometers (μm) or less (e.g., about 2 μm or less or about 1 μm or less).
[0126] As used herein, the term "Group" refers to a Group of the Periodic Table.
[0127] As used herein, “Group II” refers to Group IIA and Group IIB, and examples of Group II metals may be Cd, Zn, Hg, and Mg, but are not limited thereto.
[0128] As used herein, “Group III” refers to Group IIIA and Group IIIB, and examples of Group III metals may be Al, In, Ga, and Tl, but are not limited thereto.
[0129] As used herein, "Group IV" refers to Group IVA and Group IVB, and examples of Group IV metals may be Si, Ge, and Sn, but are not limited thereto. As used herein, the term "metal" may include semimetals such as Si.
[0130] As used herein, “Group I” refers to Group IA and Group IB, and examples thereof may include Li, Na, K, Rb, and Cs, but are not limited thereto.
[0131] As used herein, “Group V” refers to Group VA, and examples thereof may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.
[0132] As used herein, "Group VI" refers to Group VIA, and examples thereof may include sulfur, selenium, and tellurium, but are not limited thereto.
[0133] The term "average" used in this specification (eg, average size of quantum dots) may be an average value or a median value. In an embodiment, the average may be an "average" average value.
[0134] As used herein, quantum efficiency can be a quantum yield that can be easily measured by any commercially available equipment. Quantum efficiency (or quantum yield) can be measured in a solution state or a solid state (in a complex). In an embodiment, "quantum yield (or quantum efficiency)" can be, for example, the ratio of photons emitted by a nanostructure or a population of nanostructures to photons absorbed. In an embodiment, quantum efficiency can be determined by any method. For example, there can be two methods for measuring fluorescence quantum yield or efficiency: an absolute method and a relative method. The absolute method directly obtains the quantum yield by using an integrating sphere to detect the fluorescence of all samples. In a relative method, the fluorescence intensity of a standard sample (e.g., a standard dye) can be compared with the fluorescence intensity of an unknown sample to calculate the quantum yield of the unknown sample. Coumarin 153, coumarin 545, rhodamine 101 inner salt, anthracene and rhodamine 6G can be used as standard dyes according to their PL wavelengths, but are not limited thereto.
[0135] The quantum yield can be readily and reproducibly determined by using commercially available equipment (eg, equipment from Hitachi Co. Ltd or Hamamatsu Co. Ltd) and following the instructions provided by the manufacturer.
[0136] The FWHM and the maximum PL peak wavelength can be determined by a photoluminescence spectrum obtained by a spectrophotometer (or a fluorescence spectrophotometer).
[0137] As used herein, the expression "does not include cadmium (or other harmful heavy metals)" may refer to a situation where the concentration of cadmium (or other harmful heavy metals) may be less than or equal to about 100 ppmw (100 parts per million by weight), less than or equal to about 50 ppmw, less than or equal to about 10 ppmw, less than or equal to about 1 ppmw, less than or equal to about 0.1 ppmw, less than or equal to about 0.01 ppmw, or about zero. In embodiments, a certain amount of cadmium (or other harmful heavy metals) may be substantially absent, or if present, the amount of cadmium (or other harmful heavy metals) may be less than or equal to the detection limit or as an impurity level for a given analytical tool (e.g., inductively coupled plasma atomic emission spectrometry).
[0138] As used herein, "first absorption peak wavelength" refers to the wavelength of the first main peak appearing in the lowest energy region in the UV-Vis absorption spectrum.
[0139] Quantum dots (or semiconductor nanocrystal particles) are crystalline semiconductor materials with nanoscale dimensions. Quantum dots have a large surface area per unit volume due to their very small particle size, and therefore exhibit quantum confinement effects and (e.g., optical) properties that are different from (e.g., optical) properties of bulk materials with the same elemental composition. Quantum dots absorb light from an excitation source and then emit light corresponding to the bandgap energy of the quantum dots. Quantum dots can emit light with a theoretical quantum efficiency (QE or QY) of about 100% and high color purity (e.g., a full width at half maximum (FWHM) of less than or equal to about 40nm), and thus achieve increased luminous efficiency and improved color reproducibility.
[0140] Quantum dots have unique luminescent properties and have the potential to be applied as luminescent materials in various devices (e.g., electronic devices). Quantum dot-based light-emitting devices can provide improved display quality in terms of color purity, brightness, etc. A liquid crystal display (hereinafter, LCD) is a liquid crystal display (hereinafter, LCD) that realizes color by passing polarized light through an absorptive color filter after passing through a liquid crystal. However, due to the absorptive color filter, LCD has the problems of narrow viewing angle and low light transmittance. Therefore, using a photoluminescent color filter based on quantum dots instead of an absorptive color filter in an LCD can provide a wider viewing angle and a chance of improving brightness. Quantum dots can be dispersed in a host matrix (e.g., a host matrix including a polymer and / or an inorganic material) to form a quantum dot-polymer composite, which is then applied to an LCD.
[0141] For use in photoluminescent color filters, quantum dots having improved luminescent properties (e.g., increased light conversion efficiency, etc.) as well as stability (e.g., ability to maintain luminescent properties during a patterning process) are desired or of interest. The amount (or weight percentage) of quantum dots that can be included in a quantum dot-polymer composite may be limited for various reasons. Therefore, quantum dots that are included at a given weight and are able to exhibit improved brightness / light conversion efficiency and exhibit increased thermal stability are desired or of interest.
[0142] Currently, most quantum dots that exhibit optical properties useful in electronic devices (such as for displays) are based on cadmium or cadmium-containing quantum dots. However, cadmium is an element that causes serious environmental / health problems and is one of the restricted elements of the Restriction of Hazardous Substances Directive (RoHS) in many countries. Therefore, it is desirable and interesting to develop a cadmium-free quantum dot with improved photoluminescent properties.
[0143] Nanocrystals based on III-V groups can be one of non-cadmium-based (cadmium-free) quantum dots. Compared with cadmium-based quantum dots, III-V group quantum dots such as quantum dots based on indium phosphide (InP) are very susceptible to surface oxidation and may present poor stability (e.g., chemical stability and thermal stability). For example, the process for applying cadmium-free quantum dots to electronic devices may cause its luminescent properties to significantly deteriorate. In order to solve this problem and other technical problems, attempts have been made to passivate the core containing indium phosphide with the ZnSe / ZnS multilayer shells located around the core to increase quantum efficiency and stability (e.g., in the photoresist composition comprising core-shell quantum dots). However, the inventors have found that many such attempts may not be able to achieve the improvement of the luminescent properties of the desired or required level. Without wishing to be bound by any theory, this is because: compared with cadmium-based core-shell quantum dots, the InP core as the luminescent center is very easily oxidized and tends to have a large amount of surface defects. Therefore, there may be a certain technical threshold to improve luminescent properties by the presence and use of multilayer shells. In addition, in order to make core-shell quantum dots (especially, in the form of polymer composites including core-shell quantum dots, etc.) emit green light in the desired wavelength range, it may be necessary to have an indium phosphide core of relatively small size, but the smaller size of the core may lead to an increased surface area relative to the volume (i.e., an increased number of surface defects per unit volume). Therefore, a potential solution to improve the luminescent properties of cadmium-free quantum dots may lead to other problems that adversely affect such properties. In summary, the synthesis of core-shell quantum dots that can emit green light in the desired wavelength range and have improved efficiency and stability is a very difficult technical problem with no easy solution.
[0144] Core-shell quantum dots having an indium phosphide-based core and a Zn, Se, and S-based shell may not achieve the desired improved quality (e.g., a uniform shell) due to extensive oxidation of the InP core surface before or during shell formation and the resulting surface defects. The thickness of the shell layer can be increased to ensure coating uniformity, but because high absorptivity of each quantum dot is considered necessary and an increase in shell thickness may reduce absorptivity, the quantum dots obtained by such efforts may not be suitable for use as quantum dot color filters. Therefore, research and development of quantum dots having relatively thin shells (which will include a greater number of quantum dots per unit weight and exhibit a desired level of luminous efficiency and stability) (e.g., suitable for quantum dot color filters) is needed and urgently desired.
[0145] The quantum dot-polymer composite of the embodiment includes core-shell quantum dots to be described below, and thus may emit green light in a desired wavelength range with increased efficiency (eg, quantum efficiency and / or blue light conversion rate).
[0146] The quantum dot-polymer composite (or the core-shell quantum dot included therein) according to the embodiment does not include cadmium (e.g., is cadmium-free). The quantum dot-polymer composite (or the core-shell quantum dot) can emit light having a maximum peak in the green light wavelength region (e.g., when excited by blue light having a predetermined wavelength).
[0147] The blue light (excitation light) may have a central wavelength greater than or equal to about 445 nm, greater than or equal to about 450 nm, greater than or equal to about 455 nm and less than or equal to about 470 nm, less than or equal to about 465 nm, less than or equal to about 460 nm, or less than or equal to about 455 nm. The central wavelength of the blue light may be 458 nm.
[0148] The green light wavelength region (maximum emission peak wavelength region) may be greater than or equal to approximately 500 nm, for example, greater than or equal to approximately 505 nm, greater than or equal to approximately 510 nm, greater than or equal to approximately 515 nm, greater than or equal to approximately 520 nm, greater than or equal to approximately 525 nm, greater than or equal to approximately 530 nm, or greater than or equal to approximately 535 nm. The green light wavelength region may be less than or equal to about 560 nm, for example, less than or equal to about 550 nm, less than or equal to about 545 nm, less than or equal to about 540 nm, less than or equal to about 539 nm, less than or equal to about 538 nm, less than or equal to about 537 nm, less than or equal to about 536 nm, less than or equal to about 535 nm, less than or equal to about 534 nm, less than or equal to about 533 nm, less than or equal to about 532 nm, less than or equal to about 531 nm, less than or equal to about 530 nm, less than or equal to about 529 nm, less than or equal to about 528 nm, less than or equal to about 527 nm, less than or equal to about 526 nm, less than or equal to about 525 nm, less than or equal to about 524 nm, less than or equal to about 523 nm, less than or equal to about 522 nm, less than or equal to about 521 nm, or less than or equal to about 520 nm.
[0149] The quantum dot-polymer composite according to an embodiment includes a polymer matrix and core-shell quantum dots (hereinafter sometimes also referred to as quantum dots) dispersed in the polymer matrix.
[0150] The quantum dots include core-shell quantum dots including a semiconductor nanocrystal core and a semiconductor nanocrystal shell, the semiconductor nanocrystal core including indium (In), zinc (Zn) and phosphorus (P), the semiconductor nanocrystal shell being disposed on the semiconductor nanocrystal core, the semiconductor nanocrystal shell including zinc, selenium and sulfur. In the core-shell quantum dots, a molar ratio of phosphorus to indium (P:In) is greater than or equal to about 0.75:1, and a molar ratio of zinc to indium (Zn:In) is greater than or equal to about 35:1.
[0151] In this specification, the molar ratio between the quantum dot component elements can be determined by any method. In an embodiment, the molar amount or molar ratio of the quantum dot elements can be confirmed by inductively coupled plasma atomic emission analysis, X-ray photoelectron spectroscopy (XPS) or electron energy loss spectroscopy (EELS).
[0152] In an embodiment, the quantum dot may have a core-multilayer shell structure having a core including InZnP, a first shell layer directly disposed on the core and including ZnSe, and a second shell layer directly disposed on the first shell layer and including ZnS. The size of the core may be greater than or equal to about 1 nanometer (nm), greater than or equal to about 1.5 nm, or greater than or equal to about 2 nm. For example, the size of the core may be less than or equal to about 4 nm, less than or equal to about 3 nm, or less than or equal to about 2.7 nm (e.g., less than or equal to about 2.5 nm). As used herein, size may refer to the size of a single particle or the average size of a plurality of particles.
[0153] The core-shell quantum dots include a ternary core of InZnP. The core of the embodiment may exhibit reduced levels of defects, so it is then used to prepare a quantum dot-polymer composite in the presence of a shell or multilayer shell, which can achieve improved levels of light conversion efficiency. In an embodiment, the InZnP ternary core may have a layer structure of InP / InZnP / InP, and therefore, in the core, the concentration gradient of Zn may increase and then decrease from the center of the core toward the surface of the core.
[0154] Without wishing to be bound by any theory, since the core-shell quantum dots of the embodiments can have a core with the above-mentioned structural characteristics, the core-shell quantum dots of the embodiments can have the composition described herein even when the size of the core is relatively small, and can therefore exhibit improved luminescence properties.
[0155] Without wishing to be bound by any theory, the core included in the core-shell quantum dots of the embodiments is manufactured by the method to be described below and can therefore have the above-mentioned structural characteristics, which include fewer surface defects or improved oxidation resistance during shell formation (e.g., washing, etc.), so that the core-shell quantum dots can exhibit improved luminescence properties.
[0156] In the core-shell quantum dots included in the composite of the embodiment, the molar ratio of phosphorus to indium may be greater than or equal to about 0.75:1, greater than or equal to about 0.76:1, greater than or equal to about 0.77:1, greater than or equal to about 0.78:1, greater than or equal to about 0.79:1, greater than or equal to about 0.8:1, greater than or equal to about 0.81:1, greater than or equal to about 0.82:1, greater than or equal to about 0.83:1, greater than or equal to about 0.84:1, greater than or equal to about 0.85:1, greater than or equal to about 0.86:1, greater than or equal to about 0.87:1, greater than or equal to about 0.88:1, greater than or equal to about 0.89:1, greater than or equal to about 0.90:1, greater than or equal to about 0.91:1, greater than or equal to about 0.92:1, greater than or equal to about 0.93:1, greater than or equal to about 0.94:1, greater than or equal to about 0.95:1, greater than or equal to about 0.96:1, greater than or equal to about 0.97:1, greater than or equal to about 0.98:1, greater than or equal to about 0.99:1, greater than or equal to about 0.10 about 0.86:1, greater than or equal to about 0.87:1, greater than or equal to about 0.88:1, greater than or equal to about 0.89:1, greater than or equal to about 0.9:1, greater than or equal to about 0.91:1, greater than or equal to about 0.92:1, greater than or equal to about 0.93:1, greater than or equal to about 0.94:1, greater than or equal to about 0.95:1, greater than or equal to about 0.96:1, greater than or equal to about 0.97:1, greater than or equal to about 0.98:1 or greater than or equal to about 0.99:1. The molar ratio of phosphorus to indium may be less than or equal to about 1.5:1, less than or equal to about 1.4:1, less than or equal to about 1.3:1, less than or equal to about 1.2:1, less than or equal to about 1.19:1, less than or equal to about 1.18:1, less than or equal to about 1.17:1, less than or equal to about 1.16:1, less than or equal to about 1.15:1, less than or equal to about 1.14:1, less than or equal to about 1.13:1, less than or equal to about 1.12:1, less than or equal to about 1.11:1, less than or equal to about 1.1:1, less than or equal to about 1.09:1, less than or equal to about 1.08:1, less than or equal to about 1.07:1, less than or equal to about 1.06:1, less than or equal to about 1.05:1, less than or equal to about 1.04:1, less than or equal to about 1.03:1, less than or equal to about 1.0 2:1, less than or equal to approximately 1.01:1, less than or equal to approximately 1:1, less than or equal to approximately 0.99:1, less than or equal to approximately 0.98:1, less than or equal to approximately 0.97:1, less than or equal to approximately 0.96:1, less than or equal to approximately 0.95:1, less than or equal to approximately 0.94:1, less than or equal to approximately 0.93:1, less than or equal to approximately 0.92:1, less than or equal to approximately 0.91:1, less than or equal to approximately 0.9:1, less than or equal to approximately 0.89:1, less than or equal to approximately 0.88:1, less than or equal to approximately 0.87:1, less than or equal to approximately 0.86:1, less than or equal to approximately 0.85:1, less than or equal to approximately 0.84:1, less than or equal to approximately 0.83:1, less than or equal to approximately 0.82:1, less than or equal to approximately 0.81:1, or less than or equal to approximately 0.8:1.
[0157] In the core-shell quantum dots, the molar ratio of zinc to indium can be greater than or equal to about 35:1, greater than or equal to about 36:1, greater than or equal to about 37:1, greater than or equal to about 38:1, greater than or equal to about 39:1, greater than or equal to about 40:1, greater than or equal to about 41:1, greater than or equal to about 42:1, greater than or equal to about 43:1, greater than or equal to about 44:1, greater than or equal to about 45:1, greater than or equal to about 46:1, greater than or equal to about 47:1, greater than or equal to about 48:1, greater than or equal to about 49:1, or greater than or equal to about 50:1. The molar ratio of zinc to indium may be less than or equal to about 60:1, less than or equal to about 55:1, less than or equal to about 54:1, less than or equal to about 53:1, less than or equal to about 52:1, less than or equal to about 51 :1, less than or equal to about 50:1, less than or equal to about 49:1, less than or equal to about 48:1, less than or equal to about 47:1, less than or equal to about 46:1, or less than or equal to about 45:1.
[0158] In the core-shell quantum dots of the embodiment, the molar ratio of sulfur to selenium may be less than or equal to about 1: 1, less than or equal to about 0.9: 1, less than or equal to about 0.8: 1, less than or equal to about 0.7: 1, less than or equal to about 0.65: 1, less than or equal to about 0.61: 1, or less than or equal to about 0.6: 1. In the quantum dots of the embodiment, the molar ratio of sulfur to selenium may be greater than or equal to about 0.1: 1, greater than or equal to about 0.2: 1, greater than or equal to about 0.3: 1, greater than or equal to about 0.4: 1, or greater than or equal to about 0.5: 1.
[0159] In the core-shell quantum dots, the molar ratio of the sum of sulfur and selenium to indium [(Se+S):In] can be greater than or equal to about 10:1, greater than or equal to about 15:1, greater than or equal to about 19:1, greater than or equal to about 20:1, greater than or equal to about 21:1, greater than or equal to about 22:1, greater than or equal to about 23:1, greater than or equal to about 24:1, greater than or equal to about 25:1, greater than or equal to about 26:1, greater than or equal to about 27:1, greater than or equal to about 28:1, greater than or equal to about 29:1, or greater than or equal to about 30:1. The molar ratio of the sum of sulfur and selenium to indium [(Se+S):In] may be less than or equal to approximately 45:1, less than or equal to approximately 44:1, less than or equal to approximately 43:1, less than or equal to approximately 42:1, less than or equal to approximately 41:1, less than or equal to approximately 40:1, less than or equal to approximately 39:1, less than or equal to approximately 38:1, less than or equal to approximately 37:1, less than or equal to approximately 36:1, less than or equal to approximately 35:1, less than or equal to approximately 34:1, less than or equal to approximately 33:1, or less than or equal to approximately 32:1.
[0160] In the core-shell quantum dots of the embodiments, the semiconductor nanocrystal shell may include a first shell layer including zinc and selenium and a second shell layer disposed on the first shell layer and including zinc and sulfur. The first shell layer may be disposed directly on the core. The first shell layer may include ZnSe, ZnSeS, or a combination thereof. The first shell layer may not include sulfur (S). The core-shell quantum dots may not include gallium.
[0161] In an embodiment, the thickness of the first shell layer is 3 or more monolayers (ML), for example, 3.5 ML or more, 3.6 ML or more, 3.7 ML or more, 3.8 ML or more, 3.9 ML or more, or 4 ML or more. The thickness of the first shell layer may be about 7 ML or less, for example, about 6 ML or less or about 5 ML or less. In an embodiment, the thickness of the first shell layer may be greater than or equal to about 0.9 nm, greater than or equal to about 1 nm, greater than or equal to about 1.1 nm, or greater than or equal to about 1.2 nm and less than or equal to about 1.4 nm, less than or equal to about 1.3 nm, or less than or equal to about 1.25 nm.
[0162] The second shell may include ZnS. The second shell may not include selenium. The second shell may be directly disposed on the first shell. The second shell may be the outermost layer of the quantum dot. The thickness of the second shell may be less than about 0.7 nm, for example, less than or equal to about 0.65 nm, less than or equal to about 0.64 nm, less than or equal to about 0.63 nm, less than or equal to about 0.62 nm, less than or equal to about 0.61 nm, less than or equal to about 0.6 nm, less than or equal to about 0.59 nm, or less than or equal to about 0.58 nm.
[0163] The thickness of the second shell layer can be greater than or equal to about 0.15 nm, greater than or equal to about 0.16 nm, greater than or equal to about 0.17 nm, greater than or equal to about 0.18 nm, greater than or equal to about 0.19 nm, greater than or equal to about 0.2 nm, greater than or equal to about 0.21 nm, greater than or equal to about 0.22 nm, greater than or equal to about 0.23 nm, greater than or equal to about 0.24 nm, greater than or equal to about 0.25 nm, greater than or equal to about 0.26 nm, or greater than or equal to about 0.27 nm.
[0164] In the UV-Vis absorption spectrum of core-shell quantum dots or quantum dot-polymer composites including quantum dots according to the embodiments described herein, the valley depth (VD) defined by the following equation can be equal to or greater than 0.3 (for example, greater than or equal to about 0.4, greater than or equal to about 0.41, greater than or equal to about 0.42, greater than or equal to about 0.43, greater than or equal to about 0.44, greater than or equal to about 0.45, greater than or equal to about 0.46, greater than or equal to about 0.47, greater than or equal to about 0.48, greater than or equal to about 0.49, or greater than or equal to about 0.5).
[0165] 1-(Abs valley / Abs first )=VD
[0166] Here, Abs first is the absorbance (e.g., absorption intensity) at the first absorption peak (a), Abs valley is the absorbance at the lowest point of the valley adjacent to the first absorption peak (b).
[0167] In this specification, the valley of the UV-Vis absorption spectrum refers to a portion (2) where the slope of the tangent line of the UV-Vis absorption spectrum curve changes from a negative value to a positive value as the wavelength increases, and the portion (2) is adjacent to the first absorption peak (1). Figure 1 .
[0168] In the UV-Vis absorption spectrum of the core-shell quantum dots (or a composite including the same), the first absorption peak may exist in a range greater than about 450 nm and less than the maximum photoluminescence peak wavelength. The first absorption peak may be greater than or equal to about 455 nm, for example, greater than or equal to about 460 nm, greater than or equal to about 465 nm, greater than or equal to about 470 nm, greater than or equal to about 475 nm, greater than or equal to about 480 nm, greater than or equal to about 485 nm, or greater than or equal to about 490 nm and less than or equal to about 520 nm, less than or equal to about 515 nm, or less than or equal to about 510 nm.
[0169] The valley adjacent to the first absorption peak (or the lowest point of the valley) may exist within a wavelength range greater than or equal to about 420 nm, for example, greater than or equal to about 425 nm, greater than or equal to about 430 nm, or greater than or equal to about 440 nm and less than or equal to about 490 nm, for example, less than or equal to about 495 nm, less than or equal to about 480 nm, less than or equal to about 475 nm, or less than or equal to about 470 nm.
[0170] The core-shell quantum dots of the embodiment can form a population with improved size distribution. The quantum dot population includes core-shell quantum dots comprising a semiconductor nanocrystal core and a semiconductor nanocrystal shell, the semiconductor nanocrystal core includes indium (In), zinc (Zn) and phosphorus (P), the semiconductor nanocrystal shell is disposed on the semiconductor nanocrystal core, the shell includes zinc, selenium and sulfur, the core-shell quantum dots do not include cadmium, the core-shell quantum dots have a molar ratio of phosphorus to indium greater than or equal to about 0.75:1 and less than or equal to about 1.5:1 (or less than or equal to about 1.2:1), the core-shell quantum dots have a molar ratio of zinc to indium greater than or equal to about 33:1, and the core-shell quantum dots are configured to emit green light, the green light having a maximum (photo)luminescence peak wavelength less than or equal to about 550nm or less than or equal to about 540nm.
[0171] The maximum (photo)luminescence peak wavelength of green light may be less than or equal to about 545 nm, less than or equal to about 540 nm, less than or equal to about 535 nm, less than or equal to about 530 nm, less than or equal to about 525 nm, or less than or equal to about 520 nm. The maximum (photo)luminescence peak wavelength of green light may be greater than or equal to about 500 nm, greater than or equal to about 505 nm, or greater than or equal to about 510 nm.
[0172] The core-shell quantum dots may have a molar ratio of phosphorus to indium as described above. In the core-shell quantum dots, the molar ratio of phosphorus to indium may be greater than or equal to about 0.8:1, greater than or equal to about 0.82:1, greater than or equal to about 0.84:1, greater than or equal to about 0.86:1, greater than or equal to about 0.88:1, greater than or equal to about 0.9:1, greater than or equal to about 0.92:1, or greater than or equal to about 0.94:1. In the core-shell quantum dots, the molar ratio of phosphorus to indium can be less than or equal to about 1.1:1, less than or equal to about 1.08:1, less than or equal to about 1.06:1, less than or equal to about 1.04:1, less than or equal to about 1.02:1, less than or equal to about 1:1, less than or equal to about 0.98:1, less than or equal to about 0.96:1, less than or equal to about 0.94:1, less than or equal to about 0.92:1, less than or equal to about 0.9:1, less than or equal to about 0.88:1, or less than or equal to about 0.86:1.
[0173] The core-shell quantum dots may have a molar ratio of zinc to indium as described above. In the core-shell quantum dots of the embodiment, the molar ratio of zinc to indium may be greater than or equal to about 38:1, greater than or equal to about 39:1, greater than or equal to about 40:1, greater than or equal to about 41:1, greater than or equal to about 42:1, or greater than or equal to about 43:1. In the core-shell quantum dots of the embodiment, the molar ratio of zinc to indium may be less than or equal to about 50:1, less than or equal to about 49:1, less than or equal to about 48:1, less than or equal to about 47:1, less than or equal to about 46:1, less than or equal to about 45:1, less than or equal to about 44:1, less than or equal to about 43:1, less than or equal to about 42:1, or less than or equal to about 41:1.
[0174] The core-shell quantum dots may have a molar ratio of sulfur to selenium as described above. In the core-shell quantum dots of the embodiments, the molar ratio of sulfur to selenium may be less than or equal to about 0.8:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.5:1, or less than or equal to about 0.4:1. In the core-shell quantum dots of the embodiments, the molar ratio of sulfur to selenium may be greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, or greater than or equal to about 0.3:1.
[0175] In the quantum dot population, the core-shell quantum dots may have a size (or average size) greater than or equal to about 1 nm, greater than or equal to about 2 nm, greater than or equal to about 3 nm, greater than or equal to about 4 nm, or greater than or equal to about 5 nm. The core-shell quantum dots may have a size (or average size) less than or equal to about 30 nm, for example, less than or equal to about 25 nm, less than or equal to about 24 nm, less than or equal to about 23 nm, less than or equal to about 22 nm, less than or equal to about 21 nm, less than or equal to about 20 nm, less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, less than or equal to about 16 nm, less than or equal to about 15 nm, less than or equal to about 14 nm, less than or equal to about 13 nm, less than or equal to about 12 nm, less than or equal to about 11 nm, less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, or less than or equal to about 7 nm. The size of the quantum dot may be a particle size. The size of a quantum dot (if not spherical) can be the diameter calculated by converting the two-dimensional area determined by transmission electron microscopy into a circle.
[0176] In a population of quantum dots, the quantum dots can have a standard deviation of less than or equal to about 17%, less than or equal to about 16%, less than or equal to about 15%, or less than or equal to about 14% of the average size.
[0177] The shape of the quantum dots is not particularly limited, and may be, for example, spherical, polyhedral, pyramidal, polygonal or cubic nanotubes, nanowires, nanofibers, nanosheets or combinations thereof, but is not limited thereto.
[0178] The core-shell quantum dots of the embodiments can have a quantum yield of greater than or equal to about 75%, greater than or equal to about 80%, greater than or equal to about 85%, greater than or equal to about 86%, greater than or equal to about 87%, greater than or equal to about 88%, greater than or equal to about 89%, greater than or equal to about 90%, or greater than or equal to about 95%.
[0179] The core-shell quantum dots of the embodiments may have a full width at half maximum (FWHM) of less than or equal to about 50 nm, less than or equal to about 49 nm, less than or equal to about 48 nm, less than or equal to about 47 nm, less than or equal to about 46 nm, less than or equal to about 45 nm, less than or equal to about 44 nm, less than or equal to about 43 nm, less than or equal to about 42 nm, less than or equal to about 41 nm, less than or equal to about 40 nm, less than or equal to about 39 nm, less than or equal to about 38 nm, less than or equal to about 37 nm, less than or equal to about 36 nm, less than or equal to about 35 nm, less than or equal to about 34 nm, less than or equal to about 33 nm, less than or equal to about 32 nm, less than or equal to about 31 nm, or less than or equal to about 30 nm. The quantum dots may have a full width at half maximum (FWHM) of about 5 nm to about 40 nm (e.g., about 10 nm to about 35 nm, about 15 nm to about 30 nm, or about 18 nm to about 25 nm). The core-shell quantum dot may include an organic ligand described later and / or an organic solvent described later located on the surface. The organic ligand and / or the organic solvent may be bound to the surface of the quantum dot.
[0180] In the photoluminescence spectrum of the core-shell quantum dot measured at 77K, the ratio of the peak area greater than or equal to about 650nm to the area of the maximum emission peak (hereinafter referred to as the deep well ratio) may be less than or equal to about 4%, less than or equal to about 3%, or less than or equal to about 2%. Photoluminescence analysis can be performed using a 400nm light source. In low-temperature photoluminescence analysis, deep well peaks can be identified by deconvolving the maximum PL peak in a region of about -0.45eV or more from its central wavelength. Deconvolution of the peak can be easily performed by a peak analysis tool (e.g., commercially available software or open source program), which can be commercially available or can be manufactured in a known manner. As demonstrated by the inventors, in the case of green-emitting quantum dots, the presence of a well may affect the quantum dot luminescence properties (e.g., in a composite). The well emission rate at low-temperature PL may refer to the frequency / amount of wells. Quantum dots according to embodiments may exhibit a reduced well emission rate, and XPS depth analysis may indicate a very limited level of P oxide content. These results may indicate a reduced degree of surface oxidation of the core, which may indicate a reduced well emission rate and / or improved emission properties in the final core-shell quantum dots.
[0181] The method for manufacturing core-shell quantum dots and quantum dot populations including the quantum dots includes the following steps: preparing a semiconductor nanocrystal core including indium (In), zinc (Zn) and phosphorus (P); and reacting a zinc shell precursor with at least one of a selenium precursor and a sulfur precursor (i.e., a selenium precursor, a sulfur precursor or a combination thereof) in the presence of the core and a first organic ligand (e.g., in an organic solvent) to form a semiconductor nanocrystal shell including zinc, selenium and sulfur on the semiconductor nanocrystal core.
[0182] The steps of preparing the semiconductor nanocrystal core include: preparing a zinc core precursor; preparing an indium precursor solution (or indium precursor) by heating an indium compound in the presence of a second organic ligand and an organic solvent; optionally heating the indium precursor solution; and mixing the (optionally heated) indium precursor solution with a phosphorus precursor and a zinc core precursor simultaneously or sequentially to react at a reaction temperature. Adjusting the ratio between the precursors (and optionally adjusting the mixing method between them) to obtain quantum dots having the aforementioned composition.
[0183] The reaction temperature for forming the core may be greater than or equal to about 200° C., greater than or equal to about 230° C., greater than or equal to about 240° C., or greater than or equal to about 250° C. The reaction temperature for forming the core may be less than or equal to about 300° C., for example, less than or equal to about 290° C., less than or equal to about 280° C., less than or equal to about 270° C., or less than or equal to about 260° C.
[0184] In an embodiment, the mixing of the phosphorus precursor may be performed two or more times (e.g., 3 or more times and 10 or less times). In an embodiment, the mixing of the zinc core precursor may be performed two or more times (e.g., 3 or more times and 10 or less times). In an embodiment, the method may further include adding an indium precursor to the reaction mixture once, twice, or more. Without wishing to be bound by any theory, it is believed that this additional mixing method can not only control the ratio of the total precursors, but also help achieve the aforementioned composition and ratio in the final quantum dot.
[0185] In the method, the shell may include zinc selenide formed by the reaction of a zinc shell precursor and a selenium precursor, and / or the shell may include zinc sulfide formed by the reaction of a zinc shell precursor and a sulfur precursor. In an embodiment, the shell formation may be performed by reacting a zinc shell precursor with a selenium precursor and a sulfur precursor sequentially or simultaneously. Details of the types of precursors used for shell formation, etc. are described below.
[0186] In an embodiment, the zinc shell precursor and the sulfur precursor can react in an organic solvent in the presence of an acid-base adduct and a zinc halide to form a zinc sulfide shell layer. When forming the shell, the ratio between the precursors can be adjusted so that the final quantum dot can have the above composition.
[0187] In an embodiment, when the zinc shell precursor and the sulfur precursor react, the zinc shell precursor may not include halogen. In this case, the shell forming reaction system may further include a halide of an additional metal and a Lewis base, and the additional metal may include aluminum, magnesium, gallium, antimony, titanium, or a combination thereof. The Lewis base may include R 3 PO (wherein R is a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof). During the reaction of the zinc shell precursor and the sulfur precursor, a zinc halide may be additionally injected into the reaction system. The zinc halide may include zinc chloride.
[0188] The halogen-free zinc shell precursor may include dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc sulfate, or a combination thereof. The halogen-free zinc shell precursor may include a reaction product of a zinc compound (e.g., zinc acetate) and a fatty acid (e.g., a monocarboxylic acid having 10 or more carbon atoms, such as stearic acid, oleic acid, palmitic acid, lauric acid). The reaction of the zinc compound and the fatty acid may be performed in an organic solvent at a temperature greater than or equal to about 120° C. for a predetermined time.
[0189] In this case, the sulfur precursor can be obtained by contacting sulfur with a compound that can serve as a Lewis base (hereinafter referred to as a Lewis base compound). The Lewis base compound may include a primary, secondary or tertiary phosphine or a primary, secondary or tertiary phosphine oxide. The Lewis base compound may include R 3 P or R 3 PO or a combination thereof (wherein R is hydrogen or a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof). Here, in the aforementioned chemical formula, R includes hydrogen, a substituted or unsubstituted C1 to C40 (e.g., C6 or higher, C7 or higher, C8 or higher, C9 or higher or C10 or higher and C40 or lower, C30 or lower, C25 or lower) aliphatic hydrocarbon group (e.g., alkyl, alkenyl or alkynyl), a substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof. Sulfur may include elemental sulfur.
[0190] The contacting includes dispersing and / or stirring. The contacting may be performed at a temperature of greater than or equal to about 120°C, greater than or equal to about 130°C, greater than or equal to about 140°C, or greater than or equal to about 150°C and less than or equal to about 340°C, such as less than or equal to about 330°C, less than or equal to about 320°C, less than or equal to about 310°C, less than or equal to about 300°C, less than or equal to about 290°C, less than or equal to about 280°C, less than or equal to about 270°C, less than or equal to about 260°C, less than or equal to about 250°C, less than or equal to about 240°C, less than or equal to about 230°C, less than or equal to about 220°C, less than or equal to about 210°C, or less than or equal to about 200°C. Examples of phosphine oxides may include trioctylphosphine oxide, triphenylphosphine oxide, diphenylphosphine oxide, or combinations thereof, but are not limited thereto. Examples of phosphines may include trioctylphosphine, diphenylphosphine, or combinations thereof, but are not limited thereto.
[0191] The Lewis acid metal halide includes the above metals. The Lewis acid metal halide may include aluminum halide, magnesium halide, gallium halide, antimony halide, titanium halide, or a combination thereof.
[0192] Lewis base refers to a compound that can donate an electron pair to a Lewis acid metal halide. In an embodiment, the Lewis base may include the same compound used to form the sulfur precursor. The details of the Lewis base are the same as described with respect to the formation of the sulfur precursor. The Lewis base may include R 3 P and / or R 3 PO (wherein R is hydrogen, substituted or unsubstituted C1 to C40 (e.g., C6 or higher, C7 or higher, C8 or higher, C9 or higher or C10 or higher and C40 or lower, C30 or lower or C25 or lower) aliphatic hydrocarbon group (e.g., alkyl, alkenyl, alkynyl), substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof).
[0193] Lewis acid metal halides react with Lewis bases to form acid-base adducts.
[0194] The reaction conditions are not particularly limited and can be appropriately selected. The reaction temperature can be greater than or equal to about 30°C, for example, greater than or equal to about 40°C, greater than or equal to about 50°C, greater than or equal to about 60°C, greater than or equal to about 70°C, greater than or equal to about 80°C, greater than or equal to about 90°C, greater than or equal to about 100°C and less than or equal to about 300°C, less than or equal to about 200°C, less than or equal to about 150°C, less than or equal to about 140°C, less than or equal to about 130°C, less than or equal to about 120°C, or less than or equal to about 110°C.
[0195] When used, the content of zinc halide (zinc chloride) may be greater than or equal to about 10 mol%, greater than or equal to about 20 mol%, greater than or equal to about 30 mol%, or greater than or equal to about 40 mol% and less than or equal to about 100 mol%, less than or equal to about 90 mol%, less than or equal to about 80 mol%, or less than or equal to about 70 mol% relative to the sulfur precursor. When used, the content of Lewis metal halide may be greater than or equal to about 10 mol%, greater than or equal to about 20 mol%, greater than or equal to about 30 mol%, or greater than or equal to about 40 mol% and less than or equal to about 100 mol%, less than or equal to about 90 mol%, less than or equal to about 80 mol%, or less than or equal to about 70 mol% relative to the sulfur precursor.
[0196] In the method of the embodiment, when synthesizing a shell including Zn and S from a Zn shell precursor and an S precursor, a Lewis acid halide including a metal and a zinc halide may be used together in addition to the zinc shell precursor. The method can form a ZnS layer (e.g., a ZnS layer having good passivation or no defects on the shell or the outermost shell).
[0197] The type of zinc (core / shell) precursor (hereinafter referred to as zinc precursor) is not particularly limited and can be appropriately selected. For example, the zinc precursor can be Zn metal powder, alkylated Zn compound, alcohol Zn, carboxylic acid Zn, Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetone, Zn halogenation, Zn cyanide, Zn hydroxide, Zn oxidation, Zn peroxide or a combination thereof. The zinc precursor can be dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, etc. The zinc precursor can be used alone or in combination of two or more. In an embodiment, the zinc core precursor can include zinc carboxylate. The zinc core precursor can be obtained by reacting a suitable zinc compound (zinc acetate) with a carboxyl-containing organic ligand compound described later.
[0198] The (first and / or second) organic ligands may include RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3 PO, RH 2 P.R 2 HP, R 3 P, ROH, RCOOR', RPO(OH) 2 , RHPOOH, R 2POOH (wherein, R and R' are independently C1 to C40 (or C3 to C24) aliphatic hydrocarbon groups (e.g., alkyl, alkenyl or alkynyl) or C6 to C40 (or C6 to C24) aromatic hydrocarbon groups (e.g., C6 to C20 aryl)) or a combination thereof. The organic ligand can coordinate with the surface of the obtained nanocrystals and make the nanocrystals well dispersed in the solution and / or affect the photoluminescent properties and electrical properties of the quantum dots. Examples of organic ligands may include methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexylamine, octylamine, benzyl mercaptan; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, oleylamine, dimethylamine, diethylamine, dipropylamine; formic acid, acetic acid, propionic acid, butyric acid, pentyl acid, hexyl acid, heptyl acid, octyl acid, dodecyl acid, hexadecyl acid, octadecyl acid, oleic acid, benzoic acid; phosphine, such as substituted or unsubstituted methyl phosphine (e.g., trimethyl phosphine, methyl diphenyl phosphine, etc.), substituted or unsubstituted ethyl phosphine (e.g., triethyl phosphine, ethyl diphenyl phosphine, etc.), substituted or unsubstituted propyl phosphine, substituted or unsubstituted butyl phosphine, substituted or unsubstituted pentyl phosphine, substituted or unsubstituted Octylphosphine (e.g., trioctylphosphine (TOP)), etc.; phosphine oxides such as substituted or unsubstituted methylphosphine oxide (e.g., trimethylphosphine oxide, methyldiphenylphosphine oxide, etc.), substituted or unsubstituted ethylphosphine oxide (e.g., triethylphosphine oxide, ethyldiphenylphosphine oxide, etc.), substituted or unsubstituted propylphosphine oxide, substituted or unsubstituted butylphosphine oxide, substituted or unsubstituted octylphosphine oxide (e.g., trioctylphosphine oxide (TOPO)), etc.; diphenylphosphine, triphenylphosphine or their oxide compounds; C5 to C20 alkylphosphinic acid or C5 to C20 alkylphosphinic acid (such as phosphonic acid, hexylphosphinic acid, octylphosphinic acid, dodecylphosphinic acid, tetradecylphosphinic acid, hexadecylphosphinic acid, octadecylphosphinic acid, etc.); but not limited thereto. The organic ligand may be used alone or as a mixture of two or more.
[0199] The organic solvent may be selected from: C6 to C22 primary amines, such as hexadecylamine; C6 to C22 secondary amines, such as dioctylamine; C6 to C40 tertiary amines, such as trioctylamine; nitrogen-containing heterocyclic compounds, such as pyridine; C6 to C40 aliphatic hydrocarbons (e.g., alkanes, alkynes, etc.), such as hexadecane, octadecane, octadecene or squalane; C6 to C30 aromatic hydrocarbons, such as phenyldodecane, phenyltetradecane or phenylhexadecane; phosphines substituted with C6 to C22 alkyl groups, such as trioctylphosphine; phosphine oxides substituted with C6 to C22 alkyl groups, such as trioctylphosphine oxide; C12 to C22 aromatic ethers, such as phenyl ether or benzyl ether; and combinations thereof. The type and content of the organic solvent may be appropriately selected in consideration of the precursor and the organic ligand.
[0200] The type of indium compound is not particularly limited and can be appropriately selected. The indium compound may include indium powder, alkylated indium compound, indium alcohol, indium acetate, indium carboxylate, indium nitrate, indium perchlorate, indium sulfate, indium acetylacetonate, indium halide (e.g., indium chloride), indium cyanide, indium hydroxide, indium oxide, indium peroxide, indium carbonate, or a combination thereof. The indium compound is heated in the presence of an organic ligand to obtain an indium precursor. In order to form an indium precursor, the indium compound and the organic ligand may be heated in an organic solvent at a temperature of, for example, greater than or equal to about 100°C, greater than or equal to about 120°C, greater than or equal to about 150°C, greater than or equal to about 200°C, greater than or equal to about 250°C, or greater than or equal to about 270°C, under vacuum and / or an inert atmosphere.
[0201] The type of the phosphorus precursor is not particularly limited and may be appropriately selected. The phosphorus precursor may include tris(trimethylsilyl)phosphine, tris(dimethylamino)phosphine, triethylphosphine, tributylphosphine, trioctylphosphine, triphenylphosphine, tricyclohexylphosphine, or a combination thereof.
[0202] The mixture obtained by injecting the phosphorus precursor during the nucleus formation process may be heated to a temperature greater than or equal to about 50°C, greater than or equal to about 60°C, or greater than or equal to about 100°C and less than or equal to about 300°C, less than or equal to about 280°C, or less than or equal to about 260°C.
[0203] The nucleus formation reaction time is not particularly limited and may be appropriately selected in consideration of the reactivity between the precursors and the nucleus formation temperature. The nucleus formation reaction time may be greater than or equal to about 10 minutes and less than or equal to about 60 minutes.
[0204] The type of selenium precursor is not particularly limited and can be appropriately selected. For example, the selenium precursor includes selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), selenium-diphenylphosphine (Se-DPP) or a combination thereof, but is not limited thereto. In the shell formation process, the selenium precursor can be injected once or more times (e.g., twice or more times).
[0205] The sulfur precursor is not particularly limited and can be appropriately selected. In an embodiment, the sulfur precursor may include a thiol. In another embodiment, the sulfur precursor may not include a thiol. The sulfur precursor may include mercaptopropylsilane, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), sulfur-trioctylamine (S-TOA), trimethylsilylsulfide, ammonium sulfide, sodium sulfide, or a combination thereof. The sulfur precursor may be injected once or more (e.g., twice or more).
[0206] The shell formation temperature may be appropriately selected. In an embodiment, the shell formation temperature may be greater than or equal to about 220° C., greater than or equal to about 230° C., greater than or equal to about 240° C., greater than or equal to about 250° C., greater than or equal to about 260° C., greater than or equal to about 270° C., greater than or equal to about 280° C., greater than or equal to about 290° C., greater than or equal to about 300° C., greater than or equal to about 310° C., or greater than or equal to about 315° C. In an embodiment, the shell formation temperature may be less than or equal to about 350° C., less than or equal to about 340° C., less than or equal to about 330° C., or less than or equal to about 325° C.
[0207] The shell formation reaction time is not particularly limited, and can be appropriately selected. For example, the shell formation reaction can be carried out for example, greater than or equal to about 10 minutes, greater than or equal to about 20 minutes, greater than or equal to about 25 minutes, greater than or equal to about 30 minutes, greater than or equal to about 35 minutes, greater than or equal to about 40 minutes, greater than or equal to about 45 minutes, greater than or equal to about 50 minutes, greater than or equal to about 55 minutes or greater than or equal to about 1 hour, but is not limited thereto. The shell formation reaction time can be less than or equal to about 3 hours, and each precursor / compound can be added in one or more steps. When precursors are added in stages, the reaction can be carried out for a predetermined time (for example, greater than or equal to about 5 minutes, greater than or equal to about 10 minutes or greater than or equal to about 15 minutes) in each step. The reaction can be performed under an inert gas atmosphere or under air, or under vacuum, but is not limited thereto.
[0208] When a non-solvent is added to the final reaction solution obtained, the nanocrystals coordinated by the organic ligand can be separated (e.g., precipitated). The non-solvent can be a polar solvent that is miscible with the organic solvent used in the reaction and the nanocrystals cannot be dispersed therein. The non-solvent can be selected according to the organic solvent used in the reaction, and can be, for example, acetone, ethanol, butanol, isopropanol, ethylene glycol, water, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), diethyl ether, formaldehyde, acetaldehyde, a solvent with a solubility parameter similar to that of the aforementioned solvent, or a combination thereof. The separation can be performed by centrifugation, precipitation, chromatography, or distillation. If necessary, the separated nanocrystals can be added to a washing solvent and washed. The washing solvent is not particularly limited, and can have a solubility parameter similar to that of the organic ligand, and can, for example, include hexane, heptane, octane, chloroform, toluene, cyclohexane, cyclohexyl acetate, benzene, etc.
[0209] In the composite of the embodiment, the quantum dots are dispersed in a polymer matrix. The polymer matrix may include a dispersant (e.g., a binder polymer including a carboxyl group), a polymerizable monomer having a carbon-carbon double bond (at least one, for example, at least two, at least three, at least four or at least five) (e.g., an insulating polymer), and an optional polymerizable monomer (the optional polymerizable monomer is a polymerizable monomer and a polythiol compound having at least two thiol groups at the end). The quantum dot-polymer composite may also include metal oxide particles.
[0210] The polymer matrix may include a cross-linked polymer and a dispersant (e.g., a (carboxyl-containing) binder polymer). The polymer matrix may not include a conjugated polymer (except for cardo resin). The cross-linked polymer may include a thiol-olefin resin, a cross-linked poly(meth)acrylate, or a combination thereof. In an embodiment, the cross-linked polymer may be a polymerization product of a polymerizable monomer and an optional polythiol compound.
[0211] The description of the dispersant or binder polymer, polymerizable monomer and polythiol compound is the same as the description of the composition later. The content of quantum dots and the content of metal oxide particles in the composite can be relative to the content (based on solids) of the composition described later. In the composite, based on the total weight of the composite, the content of the polymer matrix can be greater than or equal to about 3 weight percent (wt%), greater than or equal to about 5 wt%, greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, or greater than or equal to about 20 wt% and less than or equal to about 97 wt%, less than or equal to about 95 wt%, less than or equal to about 90 wt%, less than or equal to about 80 wt%, or less than or equal to about 70 wt%.
[0212] The film of the quantum dot-polymer composite (or a pattern to be described later) can have a thickness of, for example, less than or equal to about 30 μm (micrometers), for example, less than or equal to about 25 μm (micrometers), less than or equal to about 20 μm, less than or equal to about 15 μm, less than or equal to about 10 μm, less than or equal to about 8 μm, or less than or equal to about 7 μm and greater than or equal to about 2 μm, for example, greater than or equal to about 3 μm, greater than or equal to about 3.5 μm, greater than or equal to about 4 μm, greater than or equal to about 5 μm, or greater than or equal to about 6 μm.
[0213] The quantum dot-polymer composite can increase the quantum efficiency by including the core-shell quantum dots described above. The quantum dot-polymer composite can have a quantum efficiency of greater than or equal to about 80%, greater than or equal to about 81%, greater than or equal to about 82%, greater than or equal to about 83%, greater than or equal to about 84%, or greater than or equal to about 85%.
[0214] After heat treatment at 180° C. for 30 minutes, the quantum dot-polymer composite may have a blue light conversion rate (blue light conversion efficiency) of greater than or equal to about 35%, greater than or equal to about 36%, or greater than or equal to about 37%.
[0215] The composition of the embodiment includes (e.g., multiple) core-shell quantum dots as described above; a dispersant (e.g., a carboxyl-containing binder polymer); and an (organic) solvent. The composition may also include a (photo)polymerizable monomer containing a carbon-carbon double bond and an optional (thermal or photo) initiator.
[0216] The content of the above quantum dots in the composition can be appropriately adjusted considering the desired end use (e.g., color filter, etc.). In an embodiment, based on the solid content of the composition, the content of the quantum dots can be greater than or equal to about 1wt%, for example, greater than or equal to about 2wt%, greater than or equal to about 3wt%, greater than or equal to about 4wt%, greater than or equal to about 5wt%, greater than or equal to about 6wt%, greater than or equal to about 7wt%, greater than or equal to about 8wt%, greater than or equal to about 9wt%, greater than or equal to about 10wt%, greater than or equal to about 15wt%, greater than or equal to about 20wt%, greater than or equal to about 25wt%, greater than or equal to about 30wt%, greater than or equal to about 35wt%, or greater than or equal to about 40wt%. Based on the solid content of the composition, the content of the quantum dots can be less than or equal to about 70wt%, for example, less than or equal to about 65wt%, less than or equal to about 60wt%, less than or equal to about 55wt%, or less than or equal to about 50wt%. The solid content of the composition of the present specification may mean the content of a corresponding component in a composite which will be described later.
[0217] The composition according to the embodiment can be used to manufacture quantum dot-polymer composite patterns. The composition according to the embodiment can be a photoresist composition containing quantum dots to which a photolithography method can be applied. The composition according to the embodiment can be an ink composition that can provide a pattern by printing (for example, a droplet discharge method using inkjet printing as an example). The composition according to the embodiment may not include a conjugated polymer (except for the cardo adhesive to be described later). The composition according to the embodiment can include a conjugated polymer. Here, a conjugated polymer refers to a polymer having conjugated double bonds in its main chain (for example, polyphenylene vinylene, etc.).
[0218] The composition according to the embodiment may include a dispersant or an adhesive polymer. The adhesive polymer may include a carboxyl group (hereinafter, a carboxyl-containing polymer). The adhesive polymer may include: a copolymer of a monomer mixture, the monomer mixture including a first monomer, a second monomer, and an optional third monomer, the first monomer including a carboxyl group and a carbon-carbon double bond, the second monomer including a carbon-carbon double bond and a hydrophobic portion and excluding a carboxyl group, and the third monomer including a carbon-carbon double bond and a hydrophilic portion and excluding a carboxyl group;
[0219] A polymer containing multiple aromatic rings (hereinafter, cardo binder) having a backbone structure in which two aromatic rings are bonded to a quaternary carbon atom which is a constituent atom of another ring portion in the main chain and including a carboxyl group (—COOH); or
[0220] A combination of them.
[0221] The copolymer includes a first repeating unit derived from a first monomer and a second repeating unit derived from a second monomer and optionally a third repeating unit derived from a third monomer.
[0222] The binder polymer including a carboxyl group may include a polymer including multiple aromatic rings. The polymer including multiple aromatic rings is known as a cardo binder resin and is commercially available.
[0223] The carboxyl-containing polymer may have an acid value of greater than or equal to about 50 mg KOH / g. For example, the carboxyl-containing polymer may have an acid value of greater than or equal to about 60 mg KOH / g, greater than or equal to about 70 mg KOH / g, greater than or equal to about 80 mg KOH / g, greater than or equal to about 90 mg KOH / g, greater than or equal to about 100 mg KOH / g, greater than or equal to about 110 mg KOH / g, greater than or equal to about 120 mg KOH / g, greater than or equal to about 125 mg KOH / g, or greater than or equal to about 130 mg KOH / g. The acid value of the carboxyl-containing polymer may be, for example, less than or equal to about 250 mg KOH / g, such as less than or equal to about 240 mg KOH / g, less than or equal to about 230 mg KOH / g, less than or equal to about 220 mg KOH / g, less than or equal to about 210 mg KOH / g, less than or equal to about 200 mg KOH / g, less than or equal to about 190 mg KOH / g, less than or equal to about 180 mg KOH / g, or less than or equal to about 160 mg KOH / g, but is not limited thereto. The binder polymer may have a weight average molecular weight greater than or equal to about 1000 g / mol, such as greater than or equal to about 2000 g / mol, greater than or equal to about 3000 g / mol, or greater than or equal to about 5000 g / mol. The binder polymer may have a weight average molecular weight greater than or equal to about 1000 g / mol, for example greater than or equal to about 2000 g / mol, greater than or equal to about 3000 g / mol, or greater than or equal to about 5000 g / mol.
[0224] In the composition, based on the total solid weight of the composition, the content of the binder polymer may be greater than or equal to about 0.5wt%, such as greater than or equal to about 1wt%, greater than or equal to about 5wt%, greater than or equal to about 10wt%, greater than or equal to about 15wt%, or greater than or equal to about 20wt%, but is not limited thereto. Based on the total solid weight of the composition, the content of the binder polymer may be less than or equal to about 55wt%, such as less than or equal to about 40wt%, less than or equal to about 30wt%, less than or equal to about 33wt%, or less than or equal to about 30wt%.
[0225] In the composition, the polymerizable (eg, photopolymerizable) monomer including a carbon-carbon double bond may include a (eg, photopolymerizable) acrylic monomer (eg, a main monomer, an auxiliary monomer, etc.).
[0226] Based on the total solid weight of the composition, the content of the polymerizable (e.g., photopolymerizable) monomer may be greater than or equal to about 0.5 wt%, such as greater than or equal to about 1 wt% or greater than or equal to about 2 wt%. Based on the total solid weight of the composition, the content of the polymerizable (e.g., photopolymerizable) monomer may be less than or equal to about 50 wt%, such as less than or equal to about 40 wt%, less than or equal to about 30 wt%, less than or equal to about 28 wt%, less than or equal to about 25 wt%, less than or equal to about 23 wt%, less than or equal to about 20 wt%, less than or equal to about 18 wt%, less than or equal to about 17 wt%, less than or equal to about 16 wt%, or less than or equal to about 15 wt%.
[0227] The initiator in the composition can be used for the polymerization of polymerizable (e.g., photopolymerizable) monomers. An initiator is a compound that accelerates a free radical reaction (e.g., free radical polymerization of a monomer) by generating free radical chemicals under mild conditions (e.g., by heat or light). The initiator can be a thermal initiator or a photoinitiator. A photoinitiator is a compound that can initiate free radical polymerization of a polymerizable acrylic monomer and / or a thiol compound (described later) by light. The type of initiator is not particularly limited and can be appropriately selected.
[0228] In the composition, the content of the initiator may be appropriately adjusted in consideration of the type and content of the polymerizable monomer. In an embodiment, the content of the initiator may be about 0.01 wt % to about 10 wt % based on the total weight of the composition, but is not limited thereto.
[0229] The composition may further include a (multifunctional or monofunctional) thiol compound having at least one thiol group at a terminal end, metal oxide particles, or a combination thereof.
[0230] The metal oxide fine particles (hereinafter, referred to as metal oxide particles) may include TiO 2 、SiO 2 、BaTiO 3 , Ba 2 TiO 4, ZnO or a combination thereof. The metal oxide particles may have a suitably selected diameter without particular limitation. The metal oxide particles may have a diameter greater than or equal to about 100 nm, for example, greater than or equal to about 150 nm or greater than or equal to about 200 nm and less than or equal to about 1000 nm or less than or equal to about 800 nm. In the composition, based on the solid content of the composition, the content of the metal oxide particles may be greater than or equal to about 1 wt %, greater than or equal to about 5 wt %, greater than or equal to about 10 wt % or greater than or equal to about 15 wt % and less than or equal to about 35 wt %, less than or equal to about 30 wt %, less than or equal to about 20 wt %, less than or equal to about 10 wt % or less than or equal to about 5 wt %.
[0231] Based on the total solid weight of the composition, the content of the thiol compound may be greater than or equal to about 1 wt%, greater than or equal to about 5 wt%, greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, or greater than or equal to about 20 wt%. Based on the total solid weight of the composition, the content of the thiol compound may be less than or equal to about 50 wt%, less than or equal to about 40 wt%, less than or equal to about 30 wt%, less than or equal to about 25 wt%, less than or equal to about 20 wt%, or less than or equal to about 15 wt%.
[0232] The composition may also include an organic solvent (or liquid carrier). The type of organic solvent available is not particularly limited. The type and content of the organic solvent may be appropriately determined by considering the above-mentioned main components (i.e., quantum dots, dispersants, polymerizable monomers, initiators, and if used, thiol compounds) and the type and content of the additives described below. The composition may include a residual amount of solvent other than the desired content of (non-volatile) solids.
[0233] If necessary, in addition to the above components, the composition may also include various additives such as light diffusers, leveling agents or coupling agents. The content of the additives is not particularly limited and can be controlled within an appropriate range in which the additives do not adversely affect the preparation of the composition and the manufacture of the quantum dot-polymer composite and optionally the patterning of the composite.
[0234] If used, the additive may be used in an amount of greater than or equal to about 0.1 wt%, such as greater than or equal to about 0.5 wt%, greater than or equal to about 1 wt%, greater than or equal to about 2 wt%, or greater than or equal to about 5 wt%, based on the total weight of the composition, but is not limited thereto. If used, the additive may be present in an amount of less than or equal to about 20 wt%, such as less than or equal to about 19 wt%, less than or equal to about 18 wt%, less than or equal to about 17 wt%, less than or equal to about 16 wt%, or less than or equal to about 15 wt%, based on the total weight of the composition, but is not limited thereto.
[0235] The composition according to the embodiment can be manufactured by a method comprising the following steps: preparing a quantum dot dispersion comprising the above quantum dots, the above dispersant and an organic solvent; and mixing the quantum dot dispersion with an initiator, a polymerizable monomer (e.g., an acrylic monomer), an optional thiol compound, optional metal oxide particles and optional aforementioned additives. Each of the above components can be mixed sequentially or simultaneously, and the order is not particularly limited.
[0236] Specific types of compositions such as first monomers, second monomers, third monomers, carboxyl-containing polymers, acrylic monomers, initiators, solvents, thiol compounds, various types of additives, and the preparation of the compositions can refer to US-2017-0059988-A1, all of which are included herein. The composition can provide a quantum dot-polymer composite (or a pattern thereof) by (e.g., free radical) polymerization.
[0237] In an embodiment, the display device includes a light emitting element (e.g., a photoluminescent element) and an optional light source, the light emitting element including a light emitting layer, which may be optionally disposed on a (transparent) substrate, and the light emitting layer includes a film or patterned film of a quantum dot-polymer composite. If present, the light source is configured to provide incident light to the light emitting element. The incident light may have a peak wavelength greater than or equal to about 440 nm (e.g., greater than or equal to about 450 nm, greater than or equal to about 455 nm, or greater than or equal to about 460 nm) and less than or equal to about 560 nm, less than or equal to about 500 nm, less than or equal to about 480 nm, less than or equal to about 470 nm, or less than or equal to about 460 nm.
[0238] The light source may be an element that emits excitation light. The excitation light may include blue light and optionally green light. The light source may include an LED. The light source may include an organic LED (e.g., an OLED). In an embodiment, a first optical element that cuts off (e.g., absorbs or reflects) blue light and optionally green light is provided on the front side (i.e., the light-emitting surface) of the first and second parts. The light source may include an OLED (organic light emitting diode) that emits blue light and an OLED that emits green light, and in this case, an optical element that filters or removes green light is provided on the third part that emits or transmits blue light.
[0239] In an embodiment, the light emitting element may include a sheet of a quantum dot-polymer composite. The display device may further include a liquid crystal panel, and the sheet of the quantum dot-polymer composite may be disposed between the light source and the liquid crystal panel. Figure 2 An exploded view of a non-limiting display device is shown. Figure 2 The display device may have a structure in which, for example, a reflector, a light guide panel (LGP) and a blue LED light source (blue LED), a quantum dot-polymer composite sheet (QD sheet), various optical films (such as a prism, a dual brightness enhancement film (DBEF)), etc.) are stacked and a liquid crystal (LC) panel is set on them.
[0240] In an embodiment, the light emitting layer may include a quantum dot-polymer composite pattern. The pattern may include at least one repeating portion to emit light of a predetermined wavelength. The quantum dot-polymer composite pattern may include a first portion emitting a first light and / or a second portion emitting a second light. The quantum dot-polymer composite pattern may be manufactured by photolithography or inkjet as described below.
[0241] The first light and the second light have different maximum photoluminescence peak wavelengths in the photoluminescence spectrum. In an embodiment, the first light may be red light existing at a maximum photoluminescence peak wavelength of about 600 nm to about 650 nm (e.g., about 620 nm to about 650 nm), and the second light may be green light existing at a maximum photoluminescence peak wavelength of about 500 nm to about 550 nm (e.g., about 510 nm to about 550 nm). The pattern may further include a third portion that emits a third light (e.g., blue light) different from the first light and the second light. The maximum peak wavelength of the third light may be in a range of greater than or equal to about 380 nm and less than or equal to about 480 nm. Optionally, see below, the third portion may allow blue excitation light to pass through the patterned film of the quantum dot-polymer composite.
[0242] An optical element (eg, a blue light blocking layer or a first filter described later) may be provided on the front surfaces (light emitting surfaces) of the first and second portions to block (eg, reflect or absorb) blue light.
[0243] In the aforementioned display device, the light source includes a plurality of light-emitting units corresponding to the repeated parts (e.g., the first part and the second part), respectively, and the light-emitting units may include a first electrode and a second electrode each having a surface opposite to each other and an electroluminescent layer disposed between the first electrode and the second electrode. The electroluminescent layer may include an organic light-emitting material. For example, each light-emitting unit of the light source may include an electroluminescent device (e.g., an organic light-emitting diode (OLED)) structured to emit light of a predetermined wavelength (e.g., blue light, green light, or a combination thereof). The structure and material of the electroluminescent device (e.g., an organic light-emitting diode (OLED)) are known, but are not particularly limited. The light source includes an organic light-emitting diode (OLED) that emits blue light (and optionally green light).
[0244] Figure 3A and Figure 3B 3A and 3B are schematic cross-sectional views of a display device according to an embodiment. Figure 3B , the light source includes an organic light emitting diode (OLED) emitting blue light. The organic light emitting diode OLED may include: (at least two, for example, three or more) pixel electrodes 90a, 90b, 90c formed on a substrate 100; pixel defining layers 150a, 150b formed between adjacent pixel electrodes 90a, 90b, 90c; organic light emitting layers 140a, 140b, 140c formed on pixel electrodes 90a, 90b, 90c; and a common electrode 130 formed on the organic light emitting layers 140a, 140b, 140c. The thin film transistor and the substrate may be disposed below the organic light emitting diode (OLED).
[0245] A stacked structure including a quantum dot-polymer composite pattern 170 (e.g., a first portion including red quantum dots and a second portion including green quantum dots) and a substrate may be disposed on a light source. Excitation light (e.g., blue light) emitted from the light source enters the first portion and the second portion configured to emit red light and green light, respectively. The blue light emitted from the light source may pass through the third portion. An optical element 160 may be disposed on the second portion 21 emitting red light, the first portion 11 emitting green light, or a combination thereof. The optical element may be an excitation light cutoff layer or a first filter layer 310 (see FIG. 1 ) that cuts off (e.g., reflects or absorbs) the excitation light (e.g., blue light, green light, or a combination thereof). Figure 4 ). The excitation light cutoff layer (or optical element) 160 may be disposed on the upper substrate 240. The excitation light cutoff layer 160 may be disposed below the upper substrate 240 (e.g., on the bottom surface of the upper substrate 240). In an embodiment, the excitation light may include blue light and optionally green light. When the laser light includes blue light and green light, the excitation light cutoff layer may be disposed on the third portion 31.
[0246] The excitation light cutoff layer 160 may be disposed between the upper substrate 240 and the quantum dot-polymer composite pattern and on the first and second portions 11, 21 and, if necessary, the third portion 31. Details of the excitation light cutoff layer are the same as those described below for the first filter layer.
[0247] The display device can be obtained by separately manufacturing the above stacked structure and an LED or OLED (eg, emitting blue light) and then assembling them. Alternatively, the display device can be obtained by directly forming a quantum dot-polymer composite pattern on an LED or OLED.
[0248] A wiring layer including a thin film transistor and the like is formed on a substrate. The wiring layer may also include a gate line, a sustaining voltage line, a gate insulating layer, a data line, a gate electrode, a source electrode, a drain electrode, a semiconductor layer, a protective layer, and the like. Depending on the embodiment, the detailed structure of the wiring layer may vary. The gate line and the sustaining voltage line are electrically separated from each other, and the data line is insulated from and crosses the gate line and the sustaining voltage line. The gate electrode, the source electrode, and the drain electrode form a control terminal, an input terminal, and an output terminal of the thin film transistor, respectively. The drain electrode is electrically connected to a pixel electrode to be described later.
[0249] The pixel electrode may be used as an anode of a display device. The pixel electrode may be formed of a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The pixel electrode may be formed of a material having a light-blocking property such as gold (Au), platinum (Pt), nickel (Ni), tungsten (W), chromium (Cr), molybdenum (Mo), iron (Fe), cobalt (Co), copper (Cu), palladium (Pd) or titanium (Ti). The pixel electrode may have a two-layer structure in which a transparent conductive material and a material having a light-blocking property are sequentially stacked.
[0250] Between two adjacent pixel electrodes, a pixel defining layer (PDL) may overlap ends of the pixel electrodes to divide the pixel electrodes into pixel units. The pixel defining layer is an insulating layer that may electrically block at least two pixel electrodes.
[0251] The pixel defining layer covers a portion of the upper surface of the pixel electrode, and a remaining area of the pixel electrode not covered by the pixel defining layer may provide an opening. An organic light emitting layer to be described later may be formed in an area defined by the opening.
[0252] The organic light emitting layer defines each pixel region through the pixel electrode and the pixel defining layer. In other words, one pixel region can be defined as a region in which one organic emission unit layer is formed, and the organic emission unit layer contacts one pixel electrode divided by the pixel defining layer.
[0253] For example, in the display device according to the embodiment, the organic light emitting layer may be defined into first, second, and third pixel regions, and each pixel region is spaced apart from each other by a pixel defining layer with a predetermined interval.
[0254] In an embodiment, the organic light-emitting layer may emit a third light belonging to the visible light region or to the UV region. That is, each pixel region from the first pixel region to the third pixel region of the organic light-emitting layer may emit a third light. In an embodiment, the third light may be light with the highest energy in the visible light region, for example, blue light. When all pixel regions of the organic light-emitting layer are designed to emit the same light, each pixel region of the organic light-emitting layer may be formed entirely of the same or similar materials, or of materials that may exhibit the same or similar properties. Therefore, the process difficulty of forming the organic light-emitting layer may be greatly reduced, and therefore, the display device may be easily applied to large-size / large-area processes. However, the organic light-emitting layer according to the embodiment is not necessarily limited thereto, but the organic light-emitting layer may be designed to emit at least two different lights.
[0255] The organic light emitting layer includes an organic emission unit layer in each pixel region, and each organic emission unit layer may further include an auxiliary layer (eg, a hole injection layer, a hole transport layer, an electron transport layer, etc.) in addition to the light emitting layer.
[0256] The common electrode may be used as a cathode of the display device. The common electrode may be formed of a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The common electrode may be formed on the organic light emitting layer and may be integrated with the organic light emitting layer.
[0257] A planarization layer or a passivation layer (not shown) may be formed on the common electrode. The planarization layer may include an (eg, transparent) insulating material for ensuring electrical insulation from the common electrode.
[0258] In an embodiment, the display device may further include a lower substrate, a polarizing plate disposed below the lower substrate, and a liquid crystal layer disposed between the stacked structure and the lower substrate, and in the stacked structure, the photoluminescent layer may be disposed to face the liquid crystal layer. The display device may further include a polarizing plate located between the liquid crystal layer and the light emitting layer. The light source may further include an LED, and if necessary, a light guide panel may further be included.
[0259] Non-limiting examples of display devices (eg, liquid crystal display devices) according to embodiments are shown with reference to the accompanying drawings. Figure 4 2 is a schematic cross-sectional view showing a liquid crystal display according to an embodiment. Figure 4 , the display device of the embodiment includes a liquid crystal panel 200 , a polarizing plate 300 disposed under the liquid crystal panel 200 , and a backlight unit (BLU) disposed under the polarizing plate 300 .
[0260] The liquid crystal panel 200 includes a lower substrate 210, a stacked structure, and a liquid crystal layer 220 disposed between the stacked structure and the lower substrate. The stacked structure includes a transparent substrate (or upper substrate) 240 and a photoluminescent layer 230, and the photoluminescent layer 230 includes a pattern of a quantum dot-polymer composite.
[0261] The lower substrate 210 (also referred to as an array substrate) may be a transparent insulating material substrate. The substrate is the same as described above. The wiring board 211 is disposed on the upper surface of the lower substrate 210. The wiring board 211 may include a plurality of gate lines (not shown) and a plurality of data lines (not shown) defining pixel regions, a thin film transistor disposed adjacent to the intersection region of the gate lines and the data lines, and a pixel electrode for each pixel region, but is not limited thereto. The details of such a wiring board are known and are not particularly limited.
[0262] The liquid crystal layer 220 may be disposed on the wiring board 211. The liquid crystal panel 200 may include an alignment layer 221 located above and below the liquid crystal layer 220 to initially align the liquid crystal material included therein. Details of the liquid crystal layer and the alignment layer (e.g., liquid crystal material, alignment layer material, method of forming the liquid crystal layer, thickness of the liquid crystal layer, etc.) are known and are not particularly limited.
[0263] The lower polarizing plate 300 is disposed under the lower substrate. The material and structure of the polarizing plate 300 are known and are not particularly limited. A backlight unit (eg, emitting blue light) may be disposed under the polarizing plate 300.
[0264] The upper optical element (or upper polarizing plate) 300 may be disposed between the liquid crystal layer 220 and the transparent substrate 240, but is not limited thereto. For example, the upper polarizing plate may be disposed between the liquid crystal layer 220 and the photoluminescent layer 230. The polarizing plate may be any polarizer used in a liquid crystal display device. The polarizing plate may be TAC (triacetyl cellulose) having a thickness of less than or equal to about 200 μm, but is not limited thereto. In another embodiment, the upper optical element may be a coating that controls a refractive index without a polarization function.
[0265] The backlight unit includes a light source 110. The light source may emit blue light or white light. The light source may include a blue LED, a white LED, a white OLED, or a combination thereof, but is not limited thereto.
[0266] The backlight unit may further include a light guide panel 120. In an embodiment, the backlight unit may be an edge-type lighting. For example, the backlight unit may include a reflector (not shown), a light guide panel (not shown) disposed on the reflector and providing a planar light source to the liquid crystal panel 200, and / or at least one optical sheet (not shown) (e.g., a diffuser, a prism sheet, etc.) located on the light guide panel, but is not limited thereto. The backlight unit may not include a light guide panel. In an embodiment, the backlight unit may be a direct-type lighting. For example, the backlight unit may have a reflector (not shown), and may have a plurality of fluorescent lamps disposed on the reflector at regular intervals, or may have an LED operating substrate on which a plurality of light-emitting diodes may be disposed, a diffuser located on the LED operating substrate, and optionally at least one optical sheet. The details of such a backlight unit (e.g., each component of the light-emitting diode, fluorescent lamp, light guide panel, various optical sheets, and reflector) are known and are not particularly limited.
[0267] The black matrix 241 is disposed below the transparent substrate 240, and the black matrix 241 has an opening and hides the gate lines, data lines and thin film transistors of the wiring board located on the lower substrate. For example, the black matrix 241 can have a grid shape. The photoluminescent layer 230 is disposed in the opening of the black matrix 241 and has a quantum dot-polymer composite pattern, which includes a first portion (R) configured to emit a first light (e.g., red light), a second portion (G) configured to emit a second light (e.g., green light) and a third portion (B) configured to emit / transmit, for example, blue light. If necessary, the photoluminescent layer may also include at least one fourth portion. The fourth portion may include quantum dots that emit light (e.g., cyan light, magenta light, and yellow light) of a color different from the color of the light emitted from the first portion to the third portion.
[0268] In the photoluminescent layer 230, a patterned portion may be repeated corresponding to a pixel region formed on a lower substrate. A transparent common electrode 231 may be disposed on the photoluminescent color filter layer (or the photoluminescent layer).
[0269] The third portion (B) configured to emit / transmit blue light may be a transparent color filter that does not change the light emission spectrum of the light source. In this case, the blue light emitted from the backlight unit may enter in a polarized state and may be emitted as is through the polarizing plate and the liquid crystal layer. If desired, the third portion may include quantum dots that emit blue light.
[0270] If necessary, the display device may further include an (excitation) light blocking layer (blue or green light cut-off filter) or a first filter layer. The blue light blocking layer may be disposed between the bottom surfaces of the first portion (R) and the second portion (G) and the upper substrate 240 or on the top surface of the upper substrate 240. The blue light blocking layer may include a sheet having an opening corresponding to a pixel region (e.g., the third portion) displaying blue, and the blue light blocking layer may be formed on a portion corresponding to the first portion and the second portion. Figure 4 As shown in , the first filter layer may be integrally formed as an integral structure at a portion other than a portion overlapping the third portion, but is not limited thereto. At least two first filter layers may be spaced apart and disposed on each portion overlapping the first portion and the second portion.
[0271] For example, the first filter layer may block light having a portion of the wavelength region in the visible light region and transmit light having other wavelength regions. For example, the first filter layer may block blue light and transmit light other than blue light. For example, the first filter layer may transmit green light, red light, and / or yellow light which is a mixed light of green light and red light.
[0272] For example, the first filter layer may substantially block blue light having a wavelength less than or equal to about 500 nm, and may transmit light in other visible light wavelength regions greater than about 500 nm and less than or equal to about 700 nm.
[0273] For example, the first filter layer may have a transmittance of greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 90%, or even about 100% with respect to other visible light greater than about 500nm and less than or equal to about 700nm.
[0274] The first filter layer may include a polymer film including a dye and / or a pigment that absorbs light having a wavelength to be blocked. The first filter layer may block at least 80% or at least 90% (even at least 95%) of blue light having a wavelength less than or equal to about 480 nm, and the first filter layer may have a transmittance greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 90%, or even about 100% with respect to other visible light greater than about 500 nm and less than or equal to about 700 nm.
[0275] The first filter layer may block (e.g., absorb) or substantially block blue light having a wavelength less than or equal to about 500 nm, and may selectively transmit green light or red light, for example. In this case, at least two first filter layers may be spaced apart and disposed on each portion overlapping the first portion and the second portion, respectively. For example, respectively, a first filter layer that selectively transmits red light may be disposed on a portion overlapping a portion emitting red light, and a first filter layer that selectively transmits green light may be disposed on a portion overlapping a portion emitting green light. For example, the first filter layer may include at least one of a first region and a second region, wherein the first region blocks (e.g., absorbs) blue light and red light and transmits a wavelength having a predetermined range (e.g., greater than or equal to about 500 nm, greater than or equal to about 510 nm, or greater than or equal to about 515 nm and less than or equal to about 550 nm, less than or equal to about 545 nm, less than or equal to about 540 nm, less than or equal to about 535 nm, less than or equal to about 530 nm, less than or equal to about 525 nm, or less than or equal to about 535 nm). The first region may be disposed at a position overlapping with a portion emitting green light, and the second region may be disposed at a position overlapping with a portion emitting red light. The first region and the second region may be optically isolated. The first filter layer may help improve the color purity of the display device.
[0276] The first filter layer may be a reflective filter including a plurality of layers (e.g., inorganic material layers) having different refractive indices. For example, two layers having different refractive indices may be alternately stacked, or, for example, a layer having a high refractive index and a layer having a low refractive index may be alternately stacked.
[0277] When the refractive index difference between the layer with a high refractive index and the layer with a low refractive index is larger, a first filter layer with higher wavelength selectivity can be provided. The thickness and stacking number of the layer with a high refractive index and the layer with a low refractive index can be determined according to the refractive index and the reflection wavelength of each layer, for example, each layer with a high refractive index can have a thickness of about 3nm to about 300nm, and each layer with a low refractive index can have a thickness of about 3nm to about 300nm.
[0278] The total thickness of the first filter layer may be, for example, about 3 nm to about 10,000 nm, about 300 nm to about 10,000 nm, or about 1,000 nm to about 10,000 nm. All layers having a high refractive index may have the same thickness and the same material as one another, or may have different thicknesses and different materials from one another, and all layers having a low refractive index may have the same thickness and the same material as one another, or may have different thicknesses and different materials from one another.
[0279] The display device may further include a second filter layer (e.g., a red / green (or yellow) recycling layer) disposed between the photoluminescent layer and the liquid crystal layer (e.g., between the photoluminescent layer and an upper polarizer or polarizing plate) and transmitting at least a portion of the third light and reflecting at least a portion of the first light and the second light. The second filter layer may reflect light in a wavelength region greater than about 500 nm. The first light may be red light, the second light may be green light, and the third light may be blue light.
[0280] In the display device according to the embodiment, the second filter layer may be formed as an integrated one layer having a relatively flat surface.
[0281] In an embodiment, the second filter layer may include a single layer having a low refractive index, for example, the second filter layer may be a transparent film having a refractive index less than or equal to about 1.4, less than or equal to about 1.3, or less than or equal to about 1.2.
[0282] The second filter layer having a low refractive index may be, for example, porous silicon oxide, a porous organic material, a porous organic / inorganic composite, or a combination thereof.
[0283] In an embodiment, the second filter layer may include multiple layers with different refractive indices, for example, the second filter layer may be formed by alternately stacking two layers with different refractive indices, or for example, the second filter layer may be formed by alternately stacking a material with a high refractive index and a material with a low refractive index.
[0284] The layer with a high refractive index in the second filter layer may include, for example, at least one of hafnium oxide, tantalum oxide, titanium oxide, zirconium oxide, magnesium oxide, cesium oxide, lanthanum oxide, indium oxide, niobium oxide, aluminum oxide and silicon nitride, but according to an embodiment, the layer with a high refractive index may include various materials having a refractive index higher than that of the layer with a low refractive index.
[0285] The layer having the low refractive index in the second filter layer may include, for example, silicon oxide, but according to embodiments, the layer having the low refractive index may include various materials having a lower refractive index than that of the layer having the high refractive index.
[0286] As the refractive index difference between the layer having a high refractive index and the layer having a low refractive index is larger, the second filter layer may have higher wavelength selectivity.
[0287] In the second filter layer, the respective thicknesses of the layers with a high refractive index and the layers with a low refractive index and the number of stacking thereof may be determined according to the refractive index and the reflection wavelength of each layer, for example, each layer with a high refractive index in the second filter layer may have a thickness of about 3 nm to about 300 nm, and each layer with a low refractive index in the second filter layer may have a thickness of about 3 nm to about 300 nm. The total thickness of the second filter layer may be, for example, about 3 nm to about 10000 nm, about 300 nm to about 10000 nm, or about 1000 nm to about 10000 nm. Each of the layers with a high refractive index and the layers with a low refractive index in the second filter layer may have the same thickness and material as each other or different thicknesses and materials from each other.
[0288] The second filter layer may reflect at least a portion of the first light (R) and the second light (G), and transmit at least a portion (e.g., all) of the third light (B). For example, the second filter layer may transmit only the third light (B) in a blue light wavelength region less than or equal to about 500 nm, while light in a wavelength region greater than about 500 nm (i.e., green light (G), yellow light, red light (R), etc.) may not pass through the second filter layer and be reflected. Therefore, the reflected green light and red light may pass through the first portion and the second portion to be emitted to the outside of the display device.
[0289] The second filter layer may reflect greater than or equal to about 70%, greater than or equal to about 80%, or greater than or equal to about 90%, or even about 100% of light in the wavelength region greater than about 500 nm.
[0290] At the same time, the second filter layer can have a transmittance of, for example, greater than or equal to about 90%, greater than or equal to about 92%, greater than or equal to about 94%, greater than or equal to about 96%, greater than or equal to about 98%, greater than or equal to about 99%, or even about 100% for light in a wavelength region less than or equal to about 500 nm.
[0291] In another embodiment, the above quantum dot-polymer composite pattern can be manufactured by a method using a photoresist composition. The method may include: forming a film of the above composition on a substrate; exposing a selected area of the film to light (e.g., light with a wavelength less than or equal to about 400 nm); and developing the exposed film with an alkaline developer to obtain a pattern of the quantum dot-polymer composite.
[0292] The substrate and composition are the same as described above. Figure 5A non-limiting method of forming the above-described pattern is shown.
[0293] The above composition is coated on a substrate to have a predetermined thickness by a suitable method such as spin coating or slit coating (S1). Optionally, the formed film may be pre-baked (PRB) (S2). Pre-baking may be performed by selecting suitable conditions from known conditions such as temperature, time, atmosphere, etc.
[0294] Under a mask having a predetermined pattern, the formed (or optionally pre-baked) film is exposed to light having a predetermined wavelength (S3). The wavelength and intensity of the light may be selected in consideration of the type and content of the photoinitiator, the type and content of the quantum dots, etc.
[0295] The exposed film is treated with an alkaline developer (e.g., dipping or spraying) to dissolve the unexposed area and obtain the desired pattern (S4). Optionally, the obtained pattern can be post-baked (POB) for a predetermined time (e.g., greater than or equal to about 10 minutes or greater than or equal to about 20 minutes) (S5) at, for example, greater than or equal to about 150°C (e.g., greater than or equal to about 180°C) and less than or equal to about 230°C (e.g., less than or equal to greater than 200°C) to improve the crack resistance and solvent resistance of the pattern. The quantum dot-polymer composite including the quantum dots of the embodiment can also exhibit a blue light conversion rate greater than or equal to about 29%, for example, greater than or equal to about 30% or greater than or equal to about 31% even after heat treatment at 180°C for 30 minutes.
[0296] When the quantum dot-polymer composite pattern has multiple repeating parts, a quantum dot-polymer composite having a desired pattern can be obtained by preparing multiple compositions including quantum dots having desired photoluminescent properties (photoluminescent peak wavelength, etc.) to form each repeating part (e.g., red-emitting quantum dots, green-emitting quantum dots, or optionally blue-emitting quantum dots); and repeating the formation of the above pattern for each composition a necessary number of times (e.g., two or more times or three or more times) (S6). For example, the quantum dot-polymer composite pattern can have a pattern of at least two repeating color parts (e.g., RGB parts). The quantum dot-polymer composite pattern can be used as a photoluminescent color filter in a display device.
[0297] In another embodiment, the above stacked structure can be manufactured using an ink composition. The method may include depositing the ink composition (e.g., to provide a desired pattern) on a desired substrate using an appropriate system (e.g., a droplet discharge device such as an inkjet or nozzle printing device) and heating it to remove the solvent and perform polymerization. The method can provide a highly accurate quantum dot-polymer composite film or pattern in a short time in a simple manner.
[0298] Another embodiment provides an electronic device including the quantum dots described above. The device may include a light emitting diode (LED), an organic light emitting diode (OLED), a sensor, a solar cell, an imaging sensor, or a liquid crystal display (LCD), but is not limited thereto.
[0299] Hereinafter, the embodiments are explained in more detail with reference to examples. However, they are exemplary embodiments of the present invention, and the present invention is not limited thereto.
[0300] Example
[0301] Analytical methods
[0302] [1] UV-Vis spectroscopy
[0303] UV-Vis spectral analysis was performed by using an Agilent Cary 5000 spectrophotometer.
[0304] [2] Photoluminescence analysis
[0305] The photoluminescence (PL) spectra of the fabricated quantum dots at an excitation wavelength of 450 nm were obtained using a Hitachi F-7000 spectrophotometer.
[0306] [3]ICP-AES analysis
[0307] Inductively coupled plasma-atomic emission spectroscopy (ICP-AES) was performed using a Shimadzu ICPS-8100.
[0308] [4] Blue light absorption rate and blue light conversion rate of the composite
[0309] The amount of blue excitation light (B) was measured using an integrating sphere. Subsequently, the QD polymer complex was placed in an integrating sphere and irradiated with blue excitation light to measure the amount of green light (or red light) emitted from the complex (A) and the amount of blue light also emitted from the complex (B').
[0310] The blue light absorption rate and the blue light conversion rate were calculated using the measured values according to the following equations.
[0311] Blue light absorption rate = (B-B') / B
[0312] Blue light conversion rate = A / B
[0313] [4] QE measurement of quantum dot-polymer composites
[0314] A quantum dot-polymer composite having a single film is manufactured (for example, by the method described below), and the quantum efficiency (QE) of the quantum dot-polymer composite is measured by using an integrating sphere.
[0315] [5] Low temperature PL analysis
[0316] A PL device equipped with low temperature measurement (manufacturer: Hitachi Tech Co., Ltd. model name: F7000) was used. The sample loaded in the MR tube was installed in the optical path area filled with liquid nitrogen to perform low temperature PL analysis at 77 K. The obtained PL peak was deconvoluted into a peak at -0.45 eV and a main peak, and then the area of each curve was integrated to obtain the deep well ratio.
[0317] [6] Transmission electron microscopy (TEM) analysis
[0318] Transmission electron microscopy analyses were performed using a UT F30 Tecnai electron microscope.
[0319] Example 1
[0320] Example 1-1: Preparation of InZnP core
[0321] Zinc acetate and oleic acid were dissolved in 1-octadecene (ODE) in a 200 milliliter (mL) reaction flask, heated at 120° C. under vacuum, and then cooled to room temperature to obtain a zinc oleate solution.
[0322] In a reaction flask, indium acetate and lauric acid and zinc oleate solutions were heated at 120°C under vacuum. Indium and lauric acid were used in a 1:3 molar ratio. After 1 hour under vacuum, nitrogen was added to the reaction flask, and tris(trimethylsilyl)phosphine ((TMSi) 3 A mixed solution of indium oleate solution, indium oleate solution, (TMSi) and trioctylphosphine (TOP) and an optional zinc oleate solution are quickly added to the reaction flask. During the reaction, the indium oleate solution, (TMSi) 3 Mixed solution of P and TOP and zinc oleate solution. The total reaction time is 30 minutes.
[0323] Indium, zinc and phosphorus were used in a molar ratio of 1.15:1.5:0.9.
[0324] The obtained InZnP cores were subjected to TEM analysis. As a result, the cores had an average size of about 1.9 nm.
[0325] Example 1-2: Synthesis and Characterization of Core-Shell Quantum Dots
[0326] Selenium (Se) was dispersed in TOP at 120°C to prepare a Se / TOP solution. Sulfur (S) was dispersed in TOP to prepare an S / TOP solution. Aluminum chloride was dispersed in TOP and stirred together at 100°C to prepare an aluminum chloride-TOP adduct (hereinafter, referred to as AlCl 3-TOP).
[0327] Zinc acetate and oleic acid were dissolved in trioctylamine in a 300 mL reaction flask and vacuum treated at 120 °C for 10 min to obtain a zinc precursor. Then nitrogen (N 2 ), and the temperature was increased to 280° C., and the reaction mixture was cooled to a predetermined temperature after a predetermined time.
[0328] The InZnP core prepared in Example 1-1 and a selenium precursor (ie, a Se / TOP solution prepared by dispersing Se powder in TOP) are added to a reaction flask in a predetermined ratio, heated and reacted at a high temperature greater than or equal to 300° C. to form a ZnSe-containing layer.
[0329] When the Se precursor was exhausted from the reaction system, S / TOP solution (i.e., sulfur precursor) and 0.072 mmol (mmol) ZnCl 2 At the same time, 0.08 mmol AlCl 3 -TOP was injected into the reaction system. The reaction was carried out for a total of 1 hour to form a ZnS-containing layer including zinc sulfide.
[0330] The obtained reaction mixture was cooled to room temperature. Ethanol was added to the cooled reaction mixture to promote the formation of a precipitate. The formed precipitate mixture was centrifuged to obtain core-shell quantum dots, which were then dispersed in toluene.
[0331] In this reaction, the zinc precursor, the selenium precursor, and the sulfur precursor were used in a molar ratio of about 6:1.6:1.7. In addition, the total amount of the zinc precursor used in this preparation was about 5.3 times more (by mole) than the indium precursor used to form the core.
[0332] Excess ethanol was added to the reactant including InZnP / ZnSe / ZnS quantum dots, followed by centrifugation. After centrifugation, the supernatant was discarded, and the precipitate was dried and dispersed in chloroform or toluene to obtain a core-shell quantum dot solution (hereinafter, QD solution).
[0333] The obtained QDs were subjected to ICP-AES analysis, and the results are shown in Table 2. The obtained QDs were subjected to UV-Vis spectroscopy analysis and photoluminescence analysis, and the results are shown in Table 1. The obtained core-shell quantum dots were subjected to low-temperature PL analysis, and the results are shown in Table 1 and Figure 6 middle.
[0334] Example 1-3: Fabrication of quantum dot-polymer composites and patterns thereof
[0335] (1) Preparation of quantum dot-binder dispersion
[0336] The toluene dispersion of the core-shell quantum dots obtained in Example 1-2 was mixed with a binder (a tetrapolymer of methacrylic acid, benzyl methacrylate, hydroxyethyl methacrylate and styrene, acid value: 130 mg KOH / g, molecular weight: 8000, methacrylic acid: benzyl methacrylate: hydroxyethyl methacrylate: styrene (molar ratio) = 61.5:12:16.3:10.2) solution (polypropylene glycol monomethyl ether acetate (PGMEA) with a concentration of 30 wt%) to prepare a quantum dot-binder dispersion.
[0337] (2) Preparation of photosensitive composition
[0338] The quantum dot-binder dispersion was mixed with hexaacrylate (as a photopolymerizable monomer), ethylene glycol di-3-mercaptopropionate (hereinafter, 2T), an oxime ester compound (as an initiator), TiO 2 (as a light diffuser) and PGMEA were mixed to prepare a composition.
[0339]
[0340] Based on the solid content of the composition, the prepared composition includes 40 weight percent (wt%) quantum dots, 12.5 wt% binder polymer, 25 wt% 2T, 12 wt% photopolymerizable monomer, 0.5 wt% initiator and 10 wt% light diffuser, and the total solid content is 25 wt%.
[0341] (3) Fabrication and heat treatment of quantum dot-polymer composite patterns
[0342] Each photosensitive composition was spin-coated on a glass substrate at 150 rpm for 5 seconds to obtain a film. The film was pre-baked (PRB) at 100° C. The pre-baked films were exposed to irradiation light (wavelength: 365 nm, intensity: 100 mJ) for 1 second under a mask having a predetermined pattern (e.g., a square dot or stripe pattern), and developed in a potassium hydroxide aqueous solution (concentration: 0.043 wt%) for 50 seconds to obtain a quantum dot-polymer composite pattern (thickness: 6 μm).
[0343] The obtained pattern was heat-treated (POB) at 180° C. for 30 minutes in a nitrogen atmosphere.
[0344] Photoluminescence analysis of the obtained patterns and measurement of blue light conversion efficiency were performed, and the results are shown in Table 3.
[0345] Example 2
[0346] Core-shell quantum dots were prepared according to the same method as in Example 1-2, except that the molar ratio of S was changed to 3.06 during shell formation. The obtained QDs were subjected to ICP-AES analysis, and the results are shown in Table 2. The obtained QDs were subjected to UV-Vis spectroscopy analysis and photoluminescence analysis, and the results are shown in Table 1.
[0347] A quantum dot-polymer composite and its pattern were obtained according to the same method as in Examples 1 to 3 except that the core-shell quantum dots of Example 2 were used. For the obtained pattern, the blue light conversion efficiency of a single film was measured and the results are shown in Table 3.
[0348] Example 3
[0349] Core-shell quantum dots were prepared according to the same method as in Example 1-1 and Example 1-2, except that In:Zn:P was used in a molar ratio of 1.125:3:1.725 to form the core. The obtained QDs were subjected to ICP-AES analysis, and the results are shown in Table 2. The obtained QDs were subjected to UV-Vis spectroscopy analysis and photoluminescence analysis, and the results are shown in Table 1.
[0350] A quantum dot-polymer composite and its pattern were obtained according to the same method as in Examples 1 to 3, except that the core-shell quantum dots of Example 3 were used. For the obtained pattern, the blue light conversion efficiency of a single film was measured, and the results are shown in Table 3.
[0351] Comparative Example 1
[0352] In addition to using In:Zn:P at a molar ratio of 6:7:4.5 during the reaction of forming the core without additionally injecting the indium precursor, the zinc precursor and the phosphorus precursor, the InZnP core is obtained according to the same method as the method of Example 1-1. In addition to using the InZnP core obtained in Comparative Example 1 and using Zn:Se:S at a molar ratio of 6:1.4:2 in the shell formation, the core-shell quantum dots are obtained according to the same method as the method of Example 1-2. The core-shell quantum dots obtained in Comparative Example 1 were subjected to ICP-AES analysis, and the results are shown in Table 2. The core-shell quantum dots obtained in Comparative Example 1 were subjected to UV-Vis spectral analysis and photoluminescence analysis, and the results are shown in Table 1.
[0353] A quantum dot-polymer composite and its pattern were obtained according to the same method as Examples 1 to 3 except that the core-shell quantum dots of Comparative Example 1 were used. For the obtained pattern, the blue light conversion efficiency of a single film was measured, and the results are shown in Table 3.
[0354] Comparative Example 2
[0355] In addition to increasing the concentration of each of the indium precursor, phosphorus precursor, and zinc precursor used for core synthesis injection by 1.43 times during the reaction without multiple injections, the InZnP core is obtained according to the same method as the method of Example 1-1. In addition to using the InZnP core obtained in Comparative Example 2, and the molar ratio of the precursor Zn:Se:S used in the shell formation is 6:1.4:2, core-shell quantum dots are prepared according to the same method as the method of Example 1-2. The core-shell quantum dots obtained in Comparative Example 2 were subjected to ICP-AES analysis, and the results are shown in Table 2. The core-shell quantum dots obtained in Comparative Example 2 were subjected to UV-Vis spectral analysis and photoluminescence analysis, and the results are shown in Table 1.
[0356] A quantum dot-polymer composite and its pattern were obtained according to the same method as Examples 1 to 3 except that the core-shell quantum dots of Comparative Example 2 were used. For the obtained pattern, the blue light conversion efficiency of a single film was measured, and the results are shown in Table 3.
[0357] Table 1
[0358]
[0359]
[0360] Table 2
[0361]
[0362] Table 3
[0363]
[0364] Referring to the results of the table, the quantum dot-polymer composites including the quantum dots of Examples 1 to 3 may exhibit improved optical properties compared to the quantum dot-polymer composites including the quantum dots of Comparative Example.
[0365] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims.
Claims
1. A method for producing a core-shell quantum dot or a group of quantum dots, the method comprising the following steps: preparing semiconductor nanocrystal cores; as well as reacting a zinc shell precursor with a selenium precursor and a sulfur precursor in the presence of a semiconductor nanocrystal core and a first organic ligand to form a semiconductor nanocrystal shell including zinc, selenium and sulfur on the semiconductor nanocrystal core, The step of preparing the semiconductor nanocrystal core includes: preparing an indium precursor solution by heating an indium compound in the presence of a second organic ligand and an organic solvent; heating the indium precursor solution; and mixing the indium precursor solution with a phosphorus precursor and a zinc core precursor simultaneously or sequentially, and performing a reaction at a reaction temperature. wherein the amounts of the indium precursor solution, the phosphorus precursor, the zinc core precursor, the selenium precursor, and the sulfur precursor are adjusted to obtain core-shell quantum dots having a molar ratio of phosphorus to indium of greater than or equal to 0.75:1 and less than or equal to 1.5:1, a molar ratio of zinc to indium of greater than or equal to 35:1 and less than or equal to 60:1, and a molar ratio of the sum of sulfur and selenium to indium of greater than or equal to 10:1 and less than or equal to 45:1, wherein the zinc shell precursor does not include halogen, and The step of forming the semiconductor nanocrystal shell includes injecting a halide of an additional metal and a Lewis base during the reaction of the zinc shell precursor and the sulfur precursor. Wherein, the additional metal includes aluminum, gallium or a combination thereof, Wherein, the Lewis base includes R3P or R3PO, wherein R is a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon group, a substituted or unsubstituted C6 to C40 aromatic hydrocarbon group, or a combination thereof, and Wherein, the step of forming the semiconductor nanocrystal shell further comprises injecting zinc halide.
2. The method according to claim 1, wherein: The step of mixing the phosphorus precursor and the zinc core precursor with the indium precursor solution includes adding each of the phosphorus precursor and the zinc core precursor two or more times when performing the reaction.
3. The method according to claim 1, wherein: The molar ratio of sulfur to selenium is less than or equal to 1:
1.
4. The method according to claim 1, wherein: The molar ratio of sulfur to selenium is less than or equal to 0.9; The molar ratio of phosphorus to indium is greater than or equal to 0.8:1 and less than or equal to 1.2:1; or The molar ratio of zinc to indium is greater than or equal to 38:1 and less than or equal to 55:
1.
5. The method according to claim 1, wherein: The molar ratio of phosphorus to indium is greater than or equal to 0.8:1 and less than or equal to 0.98:
1.
6. The method according to claim 1, wherein: The molar ratio of zinc to indium is greater than or equal to 40:1 and less than or equal to 45:
1.
7. The method according to claim 1, wherein: The molar ratio of sulfur to selenium is greater than or equal to 0.
3.
8. A quantum dot-polymer composite, comprising: polymer matrix; as well as Quantum dots, dispersed in a polymer matrix, The quantum dots include core-shell quantum dots manufactured according to the method described in claim 1, the core-shell quantum dots include a semiconductor nanocrystal core and a semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the semiconductor nanocrystal core includes indium, zinc and phosphorus, and the semiconductor nanocrystal shell includes zinc, selenium and sulfur, Wherein the core-shell quantum dots do not include cadmium, and the core-shell quantum dots are configured to emit green light.
9. The quantum dot-polymer composite according to claim 8, wherein The maximum emission peak wavelength of the green light is greater than or equal to 500 nm and less than or equal to 550 nm.
10. The quantum dot-polymer composite according to claim 8, wherein The quantum efficiency of the quantum dot-polymer composite is greater than or equal to 80%.
11. The quantum dot-polymer composite according to claim 8, wherein The core-shell quantum dots are constructed to have a valley depth greater than or equal to 0.4, as defined by the following equation: 1 - (Abs valley / Abs first ) = VD Among them, VD represents valley depth, Abs first is the absorbance at the first absorption peak, and Abs valley It is the absorbance at the lowest point of the valley adjacent to the first absorption peak.
12. The quantum dot-polymer composite according to claim 8, wherein The semiconductor nanocrystal shell includes a first shell layer and a second shell layer, the first shell layer includes zinc and selenium, and the second shell layer includes zinc and sulfur and is disposed on the first shell layer.
13. The quantum dot-polymer composite according to claim 12, wherein The second shell layer has a thickness of less than 0.7 nm.
14. The quantum dot-polymer composite according to claim 8, wherein In the photoluminescence spectrum of the core-shell quantum dots measured at 77 K, a ratio of the deep well emission peak area to the total area of the maximum emission peak is less than or equal to 4%.
15. The quantum dot-polymer composite according to claim 8, wherein The polymer matrix includes a cross-linked polymer, a binder polymer having a carboxyl group, or a combination thereof.
16. A display device, comprising a light source and a light emitting element, in, A light emitting element comprises the quantum dot-polymer composite according to any one of claims 8 to 15, and Wherein, the light source is configured to provide incident light to the light emitting element.
17. The display device according to claim 16, wherein: The light emitting element comprises a sheet of quantum dot-polymer composite; or The light emitting element includes a stack structure including a substrate and a light emitting layer disposed on the substrate, the light emitting layer including a pattern of a quantum dot-polymer composite.
18. A quantum dot population, the quantum dot population being manufactured by the method according to claim 1, the quantum dot population comprising: A plurality of core-shell quantum dots, comprising a semiconductor nanocrystal core and a semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, wherein the semiconductor nanocrystal core comprises indium, zinc and phosphorus, and the semiconductor nanocrystal shell comprises zinc, selenium and sulfur, Among them, the core-shell quantum dots do not include cadmium, The core-shell quantum dots are configured to emit green light having a maximum emission peak wavelength less than or equal to 540 nm.
19. The quantum dot population of claim 18, having an average particle size greater than or equal to 5 nanometers and a standard deviation less than or equal to 17%.
20. The quantum dot population according to claim 18, wherein: The core-shell quantum dots have a quantum efficiency greater than or equal to 78%.
Citation Information
Patent Citations
Mask Pack with Symmetric Upper and Lower Halves
KR1020190142622A
Photosensitive compositions, quantum dot polymer composite pattern prepared therefrom, and electronic devices including the same
US20170059988A1
Quantum dot, manufacturing method, quantum dot-polymer composite comprising same and electronic device
CN107663452A
A cadmium free quantum dot, a manufacturing method thereof, a composition including the same, a quantum dot-polymer composite and a display device
CN110028948A